Collaborative science narrows knowledge gaps in marine biological invasions to advance a national framework - Romeu S. Ribeiro; Cristina Espírito Santo; Susana Celestino; Marta Mamede; João J. Castro; Teresa Cruz; Teresa Silva; David Jacinto; Cátia Bartilotti; Jorge Lobo-Arteaga; Miriam Tuaty-Guerra; João Canning-Clode; et al. (Marine Pollution Bulletin, 2026)

Indigenous Peoples’ stewardship of seagrass ecosystems - Federica Manca; Álvaro Fernández-Llamazares; Maricela De la Torre-Castro; Rachel Groom; Dana Lepofsky; Jordi F Pagès; David N Thomas; Mar Cabeza (Current Opinion in Environmental Sustainability, 2026)

Vasoactive intestinal peptide advances chondrogenesis and modulates pathogenic mediators in human osteoarthritis - Karolina Tecza; Cristina Rodríguez-Hernández; Raúl Villanueva-Romero; David Castro-Vázquez; Alicia Cabrera-Martín; Paula Arribas-Castaño; Mar Carrión; Irene Gutiérrez-Cañas; Raquel Largo; Valentina Calamia; Francisco J. Blanco; Rosa P. Gomariz; et al. (Journal of Molecular Medicine, 2026)

Tracking forest carbon and growth in large-scale passive restoration using multi-temporal airborne lidar - Felipe N. Begliomini; Fabian Jörg Fischer; Srinivasan Keshav; Pedro H.S. Brancalion; Paulo G. Molin; Angelica M. Almeyda Zambrano; Angélica Faria de Resende; Cassio Toledo; Catherine Torres de Almeida; Danilo Roberti Alves de Almeida; Davi Ernesto Alvarenga César; Eben N. Broadbent; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Long-term serological monitoring of Leishmania infantum in European wild rabbits (Oryctolagus cuniculus) in Mediterranean ecosystems of southern Spain - Jesús Barbero-Moyano; Moisés Gonzálvez; David Cano-Terriza; Saúl Jiménez-Ruiz; Sabrina Castro-Scholten; Débora Jiménez-Martín; Félix Gómez-Guillamón; Leonor Camacho-Sillero; Inmaculada Moreno; Mercedes Domínguez; Jonás Carmona-Pírez; Carlos Rouco; et al. (Preventive Veterinary Medicine, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Seismic evidence of fluid migration in the Barreirinhas basin, Central Brazilian Equatorial Margin - Guilherme Martins Delabrida; David Lopes de Castro; Moab Praxedes Gomes; José Paulo de Melo Goulart (Marine Geophysical Research, 2026)
The Brazilian Equatorial Margin (BEM) is an oblique-transform continental margin inherited from the Pangea breakup and the opening of the Equatorial Atlantic Ocean. Located in the central portion of the BEM, the Barreirinhas Basin is a frontier region with only three deep-water wells. Efforts have been made to understand its tectono-depositional evolution and potential for petroleum exploration. This study provides the first integrated characterization of fluid migration systems in the offshore Barreirinhas Basin, identifying and mapping seismic indicators, as well as connecting them with regional settings. We analyzed conventional 2D and 3D seismic reflection data, integrated with available well data. Additionally, seismic attributes (instantaneous amplitude, pseudo-relief, similarity, and chaos) were applied to enhance the interpretation of conventional seismic profiles. Our results show diverse fluid migration features, from deep strata to the seafloor, constrained in four main migration systems. Two systems are correlated to regional gravitational collapse. Fluid conduits, pockmarks, mounds, and faulted zones indicate focused fluid flow. A third system is developed in a region dominated by transform tectonics related to the Romanche Fracture Zone, in which dense fault networks are observed within a laterally extensive interval from the slope to the basin plain. The fourth system is located in a broad region of the basin plain, characterized by numerous seafloor mounds associated with fluid conduits and seismic indicators of hydrocarbon accumulation. These findings improve the knowledge about an underexplored basin and provide a foundation for the understanding of fluid migration systems and their implications, including marine processes and products, emplacement of igneous bodies, and hydrocarbon prospectivity.

More diverse and structurally complex forests are less tightly coupled to ENSO forcing - Pablo Salazar-Zarzosa; Salvador Arenas-Castro; Cristina C. Bastias; David Urquiza Muñoz; Aurelio Diaz Herraiz; Jorge Duran; Yuliana Mendoza; Anke Jentsch; Peter Wolff; Antonio Velasco; Gaston Cruz; Jose Luis Quero (Remote Sensing Applications: Society and Environment, 2026)

Growth of transformed Stevia rebaudiana in in vitro systems and the stimulation of steviol glycoside production with soy protein hydrolysates - Itzel Vianney Alvarado-Orea; Noelia Atilano-González; Enrique Villalobos-Amador; Julián Mario Peña-Castro; Paula N. Robledo-Narváez; Luis Alfredo Ortega-Clemente; David Paniagua-Vega; Ariana Arlene Huerta-Heredia (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Selection and Characterization of Novel Glucuronoxylomannan-Mimetic Peptides for Potential Diagnosis of Cryptococcosis - Paulo Roberto da Silva; Kássia Gonçalves de Castro; David Nascimento Silva Teixeira; Carlos Ueira Vieira; Luiz Ricardo Goulart Filho; Alexandre de Paula Rogério; Jussara Gonçalves Vieira; Luciano Pereira Rodrigues (International Journal of Peptide Research and Therapeutics, 2026)
Cryptococcus neoformans is an encapsulated fungal pathogen characterized by a thick polysaccharide capsule, primarily composed of glucuronoxylomannan (GXM), which represents its major virulence factor and a key target for immunodiagnosis. Mimetic peptides that reproduce GXM epitopes may provide standardized, stable alternatives to native polysaccharide antigens for diagnostic and therapeutic applications. This study aimed to identify and characterize novel GXM-mimetic peptides using phage display technology and evaluate their potential as synthetic reagents for the serological diagnosis of cryptococcosis. Phage display biopanning was performed through three successive cycles using a Ph.D.-7™ combinatorial library against the anti-GXM monoclonal antibody (mAb) 18B7. Selected phage clones were sequenced, and the predominant peptide motif was identified. Based on the consensus sequence, three variants were designed: a linear peptide (LP), a cyclic peptide (CP), and a double-cyclic peptide (DP). Their immunoreactivity and diagnostic performance were evaluated via enzyme-linked immunosorbent assay (ELISA), including dose-response, serum reactivity across clinical cohorts (active cryptococcosis, treated patients, and healthy controls), and competitive inhibition assays against native GXM. Biopanning resulted in significant enrichment, with the peptide PPSLYWL (CryMab 1) emerging as the predominant sequence (54.8% frequency). ELISA demonstrated dose-dependent binding of the synthetic variants to mAb 18B7 and effective discrimination between sera from active cryptococcosis patients and control groups. In competitive ELISA, the LP variant successfully inhibited antibody binding to native GXM by 50.86%, confirming its functional antigenic mimicry. The identified GXM-mimetic peptides, particularly the LP and CP variants, exhibit specific immunoreactivity and diagnostic utility. These findings support their potential as standardized, low-cost alternatives to native fungal antigens in cryptococcosis diagnosis and provide a basis for future peptide-based theranostic strategies.

The crustacean Parapenaeus longirostris as pollution sentinel in an impacted area of the NW Mediterranean Sea - David Nos; Sergi Omedes; Javier Castro-Jiménez; Montserrat Solé (Regional Studies in Marine Science, 2026)

First confirmation of Caribbean ciguatoxins in fish samples from the South Atlantic coast of Brazil - Rodrigo Hoff; David Castro; Jorge Giráldez; Jose Manuel Leão-Martins; Ana Gago-Martínez (Food Research International, 2026)

Influence of climate variability and shark interactions on artisanal deep-water fisheries in Spain's largest marine reserve - David Jiménez-Alvarado; Ana Espino-Ruano; Airam Guerra-Marrero; Julián Cabana-Gandiaga; Tomas Bañeras; José J. Castro-Hernández; Lorena Couce-Montero (Marine Environmental Research, 2026)

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

New findings on the performance of anaerobic reactors: Ecotoxicological assessment of sublethal effects of antibiotic mixtures in wastewater on freshwater invertebrates - Gleyson B. Castro; Mateus Cottorello-Fonsêca; Tallyson T.C. de Souza; David S. Alexandre; Juliano J. Corbi (Journal of Environmental Chemical Engineering, 2026)

Assessment of installable offshore solar power capacity in Spain based on maritime spatial planning - Carla Fernández-Blanco; Almudena Filgueira-Vizoso; David Cordal-Iglesias; Ana Isabel García-Diez; Daniel Fernández-Mira; Laura Castro-Santos (Journal of Cleaner Production, 2026)

Effect of agitation speed on anaerobic digestion of sewage sludge and the organic fraction of municipal solid waste at a pilot scale - Carlos Esteven Pulgarín-Muñoz; Julio César Saldarriaga-Molina; Johan Camilo Castro-Valencia; Mauricio Andres Correa-Ochoa; Juan David Echeverry-Ruiz (Waste Disposal & Sustainable Energy, 2026)

A framework for predicting greenhouse microclimate in tomato production using XGBoost, LSTM and random forest - David Castro; Angela Sanchez; Nicolas Gutierrez; Henry Mauricio Sánchez; Alejandra Baena; Sergio Diaz (Theoretical and Applied Climatology, 2026)

Assessment of water quality and microbial contamination in Santa Marta’s major rivers using conventional methods and next-generation sequencing - Miguel Mateo Rodríguez; Vanessa Urrea; Nicolas Luna; Isaac Romero; Daniela Palma Polo; Luz H. Patiño; Juan David Ramírez; Marina Muñoz; Lyda R. Castro (Environmental Science and Pollution Research, 2026)
Water quality assessment is critical for determining the suitability of water resources for human consumption. In Santa Marta, northern Colombia, limited access to potable water and sewage systems, along with poor treatment infrastructure, poses a significant risk to both urban and rural communities. In some areas, untreated water is sourced directly from rivers or cisterns. Despite being a public health concern, molecular surveillance of waterborne pathogens remains limited. In this study, we integrated next-generation sequencing (NGS) with conventional physicochemical and microbiological analyses to assess water quality in the Gaira and Manzanares rivers. A total of 24 water samples were collected from eight sites along these rivers between August 2023 and February 2024. Microbial communities were characterized using Oxford Nanopore sequencing targeting the 16S-rRNA and 18S-rRNA genes. Physicochemical variables evidenced high levels of contamination, as elevated concentrations of nitrates, phosphates, ammonium, BOD, and COD were detected across the sampling sites. Other parameters, such as pH and temperature, remained stable, while conductivity and dissolved oxygen varied across sites. Microbiological analyses indicated elevated coliform levels, and Cryptosporidium spp. DNA, but not Giardia intestinalis DNA, was detected by PCR. Sequencing analysis revealed 1080 prokaryotic and 149 eukaryotic taxa, including environmental bacteria, Escherichia-Shigella group, and important taxa like Enterocytozoon . Diversity analyses showed that prokaryotic community structure was significantly influenced by basin location (upstream vs. downstream), whereas eukaryotic communities were primarily structured by river identity. Overall, integrating NGS with conventional methods provided a comprehensive characterization of microbial diversity and contamination risks in these tropical river systems, highlighting the urgent need to strengthen water management and public health strategies in Santa Marta and similar regions.

Sex‐Specific Atlantic Salmon Upstream Passage and Fallback at a Natural Cascade After Dam Removal - Kurt C. Heim; Jonah L. Withers; William R. Ardren; Laurie A. Earley; David Minkoff; Theodore Castro‐Santos (Fisheries Management and Ecology, 2026)
In the Boquet River (NY, USA) a low‐head dam set above a ~200‐m bedrock cascade was removed in 2015. We used radio‐telemetry to assess landlocked Atlantic salmon passage at the remaining cascade (2020, 2022). Across years, 52% of males (13/25) attempted cascade passage whereas females made no discernable attempts (0/11). Attempt probability increased with stream discharge and decreased with fish size, though overall passage success was low (1/36). Shallow depths—likely owing to an artificially widened channel—appear to be limiting passage. Additionally, we transported fish upstream but observed high fallback (72%) that was associated with fish size and energetic status. Following dam removal, this cascade continues to limit upstream passage resulting in increased vulnerability to angling during migratory delay. Overall, we highlight the importance of follow‐up studies after dam removal, and that further modifications at this site may be required to improve passage.

Static liquefaction: The role of grain size polydispersity from a micro-structural perspective - Carolina Castro-Malaver; Manuel Cárdenas-Barrantes; David Cantor; Mathieu Renouf; Emilien Azéma; Carlos Ovalle; Arcesio Lizcano (Computers and Geotechnics, 2026)

Understanding the soil-plant-animal interaction for minerals in grazing lactating cows for sustainable dairy production in high-altitude Amazonian tropics smallholders - Dario Vallejo-Timarán; David Álvarez-Sánchez; Edwin Castro-Rincón; Paola Portillo-López; Filadelfo Hernández-Oviedo; José Lerma-Lasso (Tropical Animal Health and Production, 2026)

Identification of homogeneous rainfall regions in the São Francisco River Basin, Brazil, through cluster analysis - Anderson de Oliveira Pinheiro; Demetrius David da Silva; Michel Castro Moreira; Clívia Dias Coelho; Ricardo Santos Silva Amorim (Theoretical and Applied Climatology, 2026)
Precipitation is the primary source of water in a river basin and plays a key role in water resource management by affecting water availability. However, large river basins like the São Francisco River Basin in Brazil show significant variability in rainfall patterns, leading to different water supply levels across sub-regions. To identify areas with similar rainfall patterns, the k-means clustering method was used on rainfall stations throughout the basin. The clusters were validated by analyzing their means, medians, and interquartile ranges. This analysis was supported by a multi-criteria assessment using two methods: one with a correlation matrix and the other with a covariance matrix. As a result, the stations were grouped into five homogeneous clusters based on precipitation. The two clusters in the southern basin were heavily influenced by the South Atlantic Convergence Zone (SACZ). In contrast, the northern clusters were mainly affected by the Intertropical Convergence Zone (ITCZ) and orographic features such as the Borborema Plateau. The coastal cluster was influenced by the sea and trade winds blowing from east to west. Multivariate analysis showed high correlation and seasonal similarity among stations within the same cluster. Clusters 4 and 5 experienced the highest average precipitation, while clusters 1 and 2 recorded the lowest, with cluster 2 being particularly notable.

Opportunities for remote sensing to monitor freshwater water quality after extreme weather events: A systematic review - Jiatan Liang; Andres Felipe Suárez-Castro; Tim Malthus; David P. Hamilton (Journal of Hydrology, 2026)

Enhancing sulfate-rich wastewater treatment through polyvinyl alcohol -immobilized sulfidogenic granules: Optimization of reactor configuration and bioaugmentation strategies - Rebeca Castro; Lorenz Adrian; Gemma Gabriel; David Gabriel; Xavier Gamisans; Xavier Guimerà (Journal of Environmental Chemical Engineering, 2026)

Pretreatment–gasification coupling for agro-residue conversion: Insights from experimental and Aspen plus simulations - Diana Carolina Castro Mur; Carlos A. Díaz González; Diego Mauricio Yepes Maya; Rafael David Gómez Vásquez; Ana Ramos (Biomass and Bioenergy, 2026)

Nutritional and metabolic responses of sheep fed banana leaf hay treated with sodium hydroxide - Hélio Oliveira Neves; Dorismar David Alves; Fredson Vieira e Silva; Laura Lúcia dos Santos Oliveira; Luciana Castro Geraseev; Marielly Maria Almeida Moura; Gabriel Carvalho Rezende Velasquez Santos; Adriano Mendes Vasconcelos; Janiquele Soares Silva Batista; Lara Danieli Lopes Fernandes; Cléverton Lopes Lacerda; Gabriel Santos Souza David (Tropical Animal Health and Production, 2026)
Our objective was to evaluate the impacts of the treatment of banana leaf hay with levels of sodium hydroxide (NaOH) on intake, digestibility, feeding behavior, and blood parameters of sheep. Five ½ Santa Ines × Dorper sheep with body weight of 38.43 ± 4.38 kg were used in a Latin square design. Treatments were based on levels of NaOH in banana leaf hay, as follows: 0; 1.25; 2.5; 3.75 and 5%. Overall, the intakes of dry matter, organic matter, crude protein, and total digestible nutrients increased linearly ( P < 0.001) as a function of the dose NaOH. NaOH treatment of leaf hay linearly increased ( P ≤ 0.04) the digestibility coefficients of organic matter and fiber, with an increase of 11 percentage points in fiber digestibility. However, we did not observe ( P ≥ 0.33) effect of NaOH on crude protein digestibility. No effect was observed ( P ≥ 0.07) on uric acid, creatinine, cholesterol, aspartate aminotransferase or urea. Increasing the NaOH dose did not alter the eating, rumination, and idlling time of sheep ( P ≥ 0.06). However, ruminating efficiency for dry matter and fiber were increased ( P < 0.02) as a function of the increased NaOH level. Chewing characteristics (i.e., number of bolus/day, time/bolus, and chewing/bolus) were not influenced by the NaOH levels ( P ≥ 0.06). Chemical treatment of banana leaf hay with NaOH increased feed intake and fiber digestibility in sheep and it did not affect indicators of hepatic injury, while reducing blood urea concentration, suggesting improved efficiency of nitrogen utilization.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Population dynamics and life history traits of the commercially important jaguar round crab Xantho poressa (Olivi, 1792) in Gran Canaria’s Intertidal Zones (Spain) - Airam Guerra-Marrero; Ana Espino-Ruano; David Jiménez-Alvarado; Lorena Couce-Montero; José J. Castro (Regional Studies in Marine Science, 2026)

Improving regional hydrological modeling in the Iberian Peninsula using the VIC model and optimized WRF/Noah-MP parameterizations - Nicolás Tacoronte; Sonia Raquel Gámiz-Fortis; David Donaire-Montaño; Patricio Yeste; María Jesús Esteban-Parra; Yolanda Castro-Díez; Matilde García-Valdecasas Ojeda (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Chitosan content as a key modulator of gelation threshold and sustained fluconazole release in semi-IPN hydrogels - Marcelo Guerrero; Francisco Nuñez; David Filho; Ricardo Castro; Gabriela Avilés; Adolfo Marican; Esteban Vargas; Sekar Vijayakumar; Esteban F. Durán-Lara (Carbohydrate Polymers, 2026)

Streptococcus suis in free-ranging wild boars from Southern Brazil: A preliminary survey - Cassiane Elisabete Lopes; Bruna Correa Lopes; Cristine Cerva; Angélica Cavalheiro Bertagnolli; Lucas Teixeira de Castro; Rafael Pires Lima; Jean Carlo Olivo Menegatt; Márcia Regina Loiko; David Driemeier; Fabiana Quoos Mayer (Veterinary Research Communications, 2026)

Occurrence and ecological risk of pesticides in water and sediments in regions with intensive agricultural activities - Endi Adriano Fures; Rafaela Roberta Morelato; Alonso Moscon; Laila Barcelos; Miqueias de Castro da Silva; Lisiane Martins Volcão; Jonas Simon Dugatto; David Augusto Reynalte Tataje; Liziara da Costa Cabrera (Environmental Science and Pollution Research, 2026)

Strategies to build trustworthiness and increase diversity in colorectal cancer biospecimen research: a multi-phase, multi-site qualitative study - Kristi L. Roybal; Brett Nava-Coulter; Jane Roberts; Destiny Harden; Saul Castro; Anna Revette; Maria Connolly; Gina Johnson; Jennifer A. Rountree; Suzanne Brodney; Kimberly Schoolcraft; David A. Drew; et al. (Journal of Community Genetics, 2026)

Characterization of metal contaminants in the Critically Endangered angelshark (Squatina squatina): A first ecotoxicological insight - Tomas Bañeras; David Jiménez-Alvarado; Eva K.M. Meyers; Hector Toledo-Padilla; Arturo Hardisson; Dailos Gonzalez-Weller; Joanna Barker; Lucy R. Mead; Ana Espino-Ruano; Ayoze Castro-Alonso; María José-Caballero; Ángel Gutiérrez (Marine Pollution Bulletin, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Immediate and delayed biotic and environmental responses to the carbon cycle perturbation at the onset of OAE 1a – Insights from a new high-resolution record from the Western Tethys - Cristina Sequero; Sandro Froehner; José Manuel Castro; Ginés A. De Gea; María Luisa Quijano; B. David A. Naafs; Richard D. Pancost (Global and Planetary Change, 2026)

Papaya (Carica papaya L.) accessions native to Mexico with resistance to papaya ringspot virus pathotype papaya (PRSV-P) - David Sósol-Reyes; Juan A. Villanueva-Jiménez; Alejandra Soto-Estrada; Gustavo López-Romero; Elías Hernández-Castro (Genetic Resources and Crop Evolution, 2026)

“Resilience-based framework for enhancing NaTech risk management in industrial critical infrastructures” - David J. Castro Rodriguez; Antonello A. Barresi; Micaela Demichela (Environment Systems and Decisions, 2025)
Industrial facilities, once considered isolated entities, are now approached as complex socio-technical systems that involve intricate networks operating within the confines of the surrounding environment. The increasing frequency of extreme natural events due to climate change has highlighted the vulnerability of industrial plants to NaTech (natural hazards triggering technological scenarios). Current methodologies for NaTech risk assessment focus predominantly on immediate consequences, overlooking the long-term complexities that both industrial systems and their surrounding territories may face. This research proposes a resilience-based framework for NaTech risk management, considering three main stages —awareness, preparedness, recovery—and a loop for continuous learning to address the evolving NaTech challenges. Awareness emphasizes proactive vulnerability characterization under the function-location perspective. It addresses the interactions between industrial plants and multi-hazard contexts by implementing innovative methodological procedures based on qualitative, quantitative, and spatial techniques. Preparedness is supported by an innovative multi-risk tool considering the dynamic vulnerability of equipment categories to individual and overlapped interacting hazards, able to deploy the vulnerability into hierarchical safety layers to design robust and context-specific safer systems. The recovery stage is described through a retrospective case of hydrocarbon pollution caused by rainfall, integrating countermeasures and sustainable technological solutions. Overall, this research highlights the need for multidimensional approaches to tackle the evolving challenges posed by NaTech events. The outcomes present a comprehensive resilience-based framework, and operational procedures guiding the practical implementation of resilience principles and advancing the understanding of complex industrial systems while supporting their long-term sustainability facing natural factors.

Warming enhances primary production and respiration and changes plankton community structure in an estuarine upwelling system - Tanguy Soulié; Jose González; Pablo Serret; Isabel G. Teixeira; Carmen González Castro; Sébastien Mas; David Parin; Francesca Vidussi; Behzad Mostajir (Limnology and Oceanography, 2025)
Marine heatwaves are expected to become more frequent and intense due to global climate change, potentially impacting plankton communities. In the present study, the effects of a simulated short‐term warming event on the structure and functioning of coastal plankton communities were investigated during a mesocosm experiment conducted with water from the Ría de Vigo, a productive estuary strongly influenced by coastal upwelling dynamics from the North‐Western (NW) Iberian Peninsula. A warming event was simulated in triplicate mesocosms by increasing their water temperature at +3°C compared to three other mesocosms, which followed the natural temperature of the Ría. High‐frequency monitoring from sensors immersed in all mesocosms was used to estimate gross primary production (GPP), community respiration ( R ), phytoplankton growth ( μ ), and loss ( L ) rates. Phytoplankton size structure and community composition, photosynthetic efficiency, and inorganic nutrient concentrations were assessed from daily manual sampling of the mesocosms. Warming induced a mismatch between phytoplankton growth and its grazers, as it enhanced μ at the beginning of the experiment, while L only increased after a few days. Warming also significantly enhanced both GPP and R , but the metabolic index (GPP : R ratio) was not significantly affected by warming, as both GPP and R were enhanced to a similar extent. Warming altered the phytoplankton community structure by favoring haptophytes at the expense of diatoms and dinoflagellates. Conducted during phosphorus‐depleted post‐upwelling conditions, this experiment highlights the positive effects of short‐term warming events on the metabolic and trophic functioning of plankton communities from coastal upwelling systems.

Thrips (Insecta: Thysanoptera) species associated with avocado orchards in central Veracruz, Mexico - David Alarcón-Utrera; Daniel López-Lima; Carlos R. Cerdán-Cabrera; Gerardo Alvarado-Castillo; Alejandro Salinas-Castro; Gloria Carrión (International Journal of Tropical Insect Science, 2025)

Feline herpesvirus and calicivirus: Occurrence and pathology in cats with respiratory disease - Mônica Slaviero; Bruno A de Almeida; Lucas T de Castro; Welden Panziera; Saulo P Pavarini; David Driemeier; Luciana Sonne (Topics in Companion Animal Medicine, 2025)

The silent risks of urban lead and its impactful consequences in Boquira, Brazil - Ésio de Castro Paes; David Lukas de Arruda; Danilo de Lima Camêlo; Iara Oliveira Fernandes; Gustavo Vieira Veloso; Matheus da Silva Ferreira; Maurício Paulo Ferreira Fontes; Elpídio Inácio Fernandes-Filho; Mário Ferreira Conceição Santos; Emanuele Mercês Barros Soares (Environmental Geochemistry and Health, 2025)

Developmental and behavioral traits of tropical amphipod Hyalella meinerti can be impaired by polyethylene microplastics - David Silva Alexandre; Gleyson Borges Castro; Isabele Baima Ferreira Freitas; Thandy Junio da Silva Pinto; Mariana Amaral Dias; Cassiana Carolina Montagner; Evaldo Luiz Gaeta Espíndola (Ecotoxicology, 2025)

“Critical infrastructure multi-risk deployment: an innovative framework to support NaTech preparedness in industrial facilities” - David Javier Castro Rodriguez; Antonello A. Barresi; Micaela Demichela (Process Safety and Environmental Protection, 2025)

Seroepidemiological study of Chlamydia abortus in domestic and wild ruminants in Spanish Mediterranean ecosystems - Débora Jiménez-Martín; Ignacio García-Bocanegra; Saúl Jiménez-Ruiz; Javier Caballero-Gómez; Sabrina Castro-Scholten; Jorge Paniagua; Paloma Prieto-Yerro; David Cano-Terriza (Preventive Veterinary Medicine, 2025)

Eco-extraction and characterization by HPLC-HRMS/MS of in vitro culture of the carnivorous plant Drosera - Rym Attia; Alexander Castro Grijalba; David Da Silva; Laurine Garros; Christophe Hano; Arnaud Lanoue; Nathalie Giglioli-Guivarch; Emilie Destandau (Phytochemistry Letters, 2025)

Influence of local factors on the expression of the early Aptian OAE 1a – insights from a pelagic basin in the Western Tethys - José Manuel Castro; Cristina Sequero; Maria Luisa Quijano; Ginés A. de Gea; B. David A. Naafs; Richard D. Pancost (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Thermal structure of the Barreirinhas Basin, Brazilian equatorial margin - Chayane Vitória Félix Fonseca; David Lopes de Castro; Diógenes Custódio de Oliveira; Daniel Teixeira dos Santos; Heriscarth Marcell Dantas Pinheiro; Lívian Rafaely de Santana Gomes Pinheiro (Journal of South American Earth Sciences, 2025)

Supercritical water desalination and oxidation (SCWDO): Effectiveness on complex solutions, technoeconomic, and CO2 impact for produced water treatment - Prashant Sharan; Michael Dugas; Santosh Ravichandran; Raymond Castro; Ayan Biswas; David M. Warsinger; Rajinder Singh; Robert P. Currier; Alp T. Findikoglu (Desalination, 2025)

Use of Essential Oil from Aloysia citrodora Paláu in Anesthesia and Simulated Transport of Tambaqui Colossoma macropomum (Cuvier 1826) at Two Different Cargo Densities - Orlando Pinto de Almeida Castro Neto; Patrick Jordan Correia-Silva; Isabelle Santos Silva; Aline dos Anjos Santos; Aline da Silva Rocha; Ricardo David Couto; Erick dos Santos Silva; Denise Schmidt; Carlos Eduardo Copatti (Fishes, 2025)
This study evaluated the effectiveness of essential oil from Aloysia citrodora (EOAC) (48% citral and 19% limonene) for use in anesthesia and simulated transport of tambaqui (Colossoma macropomum) juveniles at two cargo densities (CDs). Concentrations of 0 (control), 10, 25, 50, 100, 150, 200, and 250 µL EOAC L−1 were tested for use in anesthesia induction and recovery, while 0 (control) and 20 µL EOAC L−1 were tested for their effects on the ventilatory rate (VR) and during 6 h simulated transport at a low CD (LCD, 65 g L−1) and standard CD (SCD, 130 g L−1). Fish were anesthetized at EOAC concentrations above 50 µL L−1, with the optimal anesthesia (141.83 s) and recovery times (160.00 s) at 250 µL L−1. The water unionized ammonia was lowest in the EOAC-LCD group. Using 20 µL EOAC L−1 during transport minimized changes in the hematological parameters (erythrocytes, hemoglobin, hematocrit, total leukocytes, and heterophils) and reduced the liver aspartate aminotransferase activity at both CDs. Transport at an SCD, regardless of EOAC use, increased the plasma glucose, hepatic glycogen, and alanine transaminase activity. The VR was higher with 20 µL EOAC L−1 than in the control group. In conclusion, our findings confirm that 20 µL EOAC L−1 can effectively be used to transport tambaqui for up to 6 h without impairing fish health.

Genomic insights into five PGPR strains from tropical soil reveal potential for root architecture modulation and sustainable agriculture - Carlos González-Cruz; Norma Flores-Estévez; Juan Carlos Noa-Carrazana; Jesús Alejandro Zamora-Briseño; Ricardo Santillán-Mendoza; Randy Ortíz-Castro; Humberto Estrella-Maldonado; Cristian Matilde-Hernández; Félix David Murillo-Cuevas; José Antonio Fernández-Viveros; Jacel Adame-García; Felipe Roberto Flores-de la Rosa (Rhizosphere, 2025)

Finding optimal Noah-MP parameterizations for the characterization of surface heat fluxes in the Iberian Peninsula - David Donaire-Montaño; Matilde García-Valdecasas Ojeda; Nicolás Tacoronte; Juan José Rosa-Cánovas; Yolanda Castro-Díez; María Jesús Esteban-Parra; Sonia Raquel Gámiz-Fortis (Atmospheric Research, 2025)

Characteristics of widespread extreme precipitation events in Peninsular Spain and the Balearic Islands: spatio-temporal dynamics and driving mechanisms - Sergio M. Vicente-Serrano; Jose M. Garrido-Perez; José Carlos Fernández-Álvarez; Luis Gimeno-Sotelo; Santiago Beguería; Amar Halifa-Marín; Borja Latorre; Ahmed M. El Kenawy; Magí Franquesa; María Adell-Michavila; Fernando Domínguez-Castro; David Barriopedro; et al. (Climate Dynamics, 2025)
This study analysed widespread extreme precipitation events (WEPEs) across Spain using a high-density network of daily precipitation records, aiming to clarify their spatiotemporal trends and drivers. The findings reveal that WEPEs in Spain show a non-significant trend in either frequency or intensity since 1961, despite the prevailing trend of global warming. Nevertheless, atmospheric circulation plays a key role in shaping WEPEs in Spain, with five distinct synoptic patterns driving extreme precipitation across different regions. Westerly flows associated with Atlantic lows lead to widespread precipitation in northern and western Spain, while cut-off lows generate intense but more localized events, particularly in the east. Jet stream anomalies and moisture transport patterns, particularly from the Mediterranean and Atlantic, further modulate the spatial distribution and intensity of WEPEs, highlighting the interaction between regional and large-scale climatic drivers. These findings highlight the importance of distinguishing between widespread and localized EPEs and the associated atmospheric mechanisms.

Genetic alterations in coronary cell lines exposed to sirolimus and paclitaxel - Elaine Aparecida de Camargo; Glenda Nicioli da Silva; João Paulo de Castro Marcondes; David Corrêa Martins; Wilson Nadruz; Roberto Schreiber; Décio Salvadori; Daisy Maria Fávero Salvadori (Archives of Toxicology, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Carbon balance in dairy cattle silvopastoral production systems in Colombia’s Andean-Amazon region - Henry Mavisoy; Adrian Rolando Riascos Vallejos; Edwin Castro Rincón; Juan Pablo Narváez-Herrera; Lorieth Rosas; Adriana del Socorro Guerra Acosta; Adrián Antonio Riascos Salcedo; Disney Magali Aguillon Alban; Carlos Chingal; David Fangueiro; André M. de Almeida (Agroforestry Systems, 2025)
Silvopastoral systems (SPS) are recognized for their potential to sequester carbon (C) and mitigate greenhouse gas (GHG) emissions in livestock production. However, the extent to which small-scale dairy farms in the Andean region can offset emissions through SPS remains unclear. This study assessed the C capture of SPS to mitigate greenhouse gas emissions in small-scale dairy farms in Colombia's Andean-Amazon region. The average annual carbon increment (AACI) in living biomass (above and below ground) was evaluated in woodlots (WL), live fences (LF), and topsoil of pastures (TP) at plot and farm levels. The carbon footprint (CFP) was calculated using a cradle-to-gate approach with biophysical allocation for fat and protein corrected milk (FPCM) and expressed per product (MgCO 2 -eq MgFPCM⁻ 1 ) and area (MgCO 2 -eq·yr⁻ 1 ha⁻ 1 ) across 30 farms categorized by high, medium, and low SPS coverage. At plot level, AACI values were 4.54 ± 0.57 Mg·C·ha⁻ 1 ·yr⁻ 1 (LF), 3.20 ± 0.61 Mg·C·ha⁻ 1 ·yr⁻ 1 (WL), and 0.24 ± 0.08 Mg·C·ha⁻ 1 ·yr⁻ 1 (TP). At farm-level AACI was 4.43 ± 0.96, 1.28 ± 0.41, and 0.24 ± 0.08 Mg·C·ha⁻ 1 ·yr⁻ 1 for high, medium, and low SPS coverages respectively. Between 78 and 86% of AACI was attributed to Eucalyptus globulus (LF). CFP per product averaged 1.24 ± 0.16 MgCO 2 -eq MgFPCM⁻ 1 . Total emissions per farm averaged 28.27 ± 2.58 MgCO 2 -eq·yr⁻ 1 and per area 3.35 ± 0.32 MgCO 2 -eq·yr⁻ 1 ha⁻ 1 , with no differences across SPS coverages. Carbon balance was negative regardless of SPS coverage. The mitigation potential of SPS were 63%, 26%, and 4% for high, medium, and low SPS coverage. The required area to offset emissions ranged from 11.5 ha⁻ 1 considering the soil AACI to 1.2–10.2 ha⁻ 1 based on the AACI of SPS. Small dairy farms (9.11 ± 0.75 ha −1 ) in the Andean-Amazon region can mitigate total emissions using a SPS coverage over 13% together with optimized feeding practices, lactation and weaning periods.

An Optimal and Flexible Approach for Drought Quantification Based on Standardised Indices - Sergio M. Vicente‐Serrano; Fergus Reig; Santiago Beguería; Ahmed El‐Kenawy; Fernando Domínguez‐Castro; Magí Franquesa; Luis Gimeno‐Sotelo; María Adell‐Michavilla; Amar Halifa‐Marín; Iván Noguera; Miguel Andres‐Martin; Cesar Azorin‐Molina; et al. (International Journal of Climatology, 2025)
In this study we propose a novel approach to standardising drought indices that offers flexibility tailored to local conditions. This involves employing different probability distributions and the Akaike Information Criterion to identify the most appropriate distribution for each region and variable. Following this approach, our proposed methodology enhances the accuracy and comparability across different spatial and temporal scales, with improved representation of extreme drought events. Nonetheless, despite the increased computational requirements associated with this approach, the advantages are substantial. By enhancing accuracy, comparability and adaptability, it may improve drought monitoring and management practices. Moreover, the methodology provides a versatile framework for standardising a wide range of environmental variables beyond traditional drought indices, and software for calculations is provided ( https://github.com/lcsc/FlexDroughtIndex ). Overall, the findings of this study can advance drought assessments by providing an innovative and flexible methodology that addresses key limitations of current approaches.

Optimization and validation of a micro-QuEChERS method coupled with LC–MS for the analysis of pesticides in fish tissue - Endi Adriano Fures; Miqueias de Castro da Silva; Lisiane Martins Volcão; Janaina Silva Sarzi; Jonas Inticher; Jonas Simon Dugatto; David Augusto Reynalte-Tataje; Liziara da Costa Cabrera (Environmental Monitoring and Assessment, 2025)

Framing social systems for ecosystem-based management: The Guadalquivir estuary-Gulf of Cadiz coupled SES as case study - Alfredo García-de-Vinuesa; David Florido; Cesar Vilas; María Ángeles Torres; Marina Delgado; Isabel Muñoz; Remedios Cabrera-Castro; Fernando Ramos; Marcos Llope (Environmental Development, 2025)

Morphological anomalies in amphibians of the Sierra Madre Occidental and a review of cases reported in Mexico - Héctor Alexis Castro-Bastidas; Marcos Bucio-Pacheco; José Manuel Serrano; David Ramiro Aguillón-Gutiérrez (Environmental Monitoring and Assessment, 2025)
The data on the incidence and diversity of anomalies in amphibian populations in Mexico are primarily derived from opportunistic observations, which pose challenges for conducting comparisons and monitoring long-term trends. In this study, we document new cases of morphological anomalies in amphibians from the Sierra Madre Occidental and provide a systematic bibliographic review of reported cases across Mexico. During the 2023 rainy season, we conducted surveys in Surutato, Sinaloa, documenting nine cases of morphological anomalies, including the first documented case of dyscoria in the country. The bibliographic review covered 34 sources and identified 31 types of anomalies, with the family Ambystomatidae being the most affected. We observed significant ambiguity in the terminology used across reports, which hinders data comparability. To address this issue, we propose promoting a standardized approach to the description and classification of anomalies. Based on the available data, we estimate a national mean anomaly frequency of 18.43% in amphibians, which can serve as a preliminary benchmark for future studies. The most commonly identified causes of anomalies include agrochemical pollution and parasitism; however, in 37% of the cases, no specific cause could be determined. These findings underscore the importance of standardizing anomaly reports, as they can serve as valuable early indicators of environmental degradation.

Chemical emissions from offshore wind farms: From identification to challenges in impact assessment and regulation - Elena Hengstmann; Pablo Zapata Corella; Katharina Alter; Maria J. Belzunce-Segarra; Andy M. Booth; Javier Castro-Jiménez; Niklas Czerner; Karien De Cauwer; Geneviève Deviller; Alessio Gomiero; Nils Goseberg; Simone Hasenbein; et al. (Marine Pollution Bulletin, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Amenity migration for land stewardship: Getting to know the new faces in ranching - David Matarrita-Cascante; Cinthy Veintimilla; Chase Brooke; Morgan Treadwell; Caitlin Castro (Rangelands, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

A “light in the darkness”: First transcriptomic data from deep-sea spiny eels (Notacanthus, Notacanthiformes) - André Gomes-dos-Santos; André M. Machado; Francisco Baldó; Juan Carlos Arronte; L. Filipe C. Castro; David Barros-García (Marine Genomics, 2025)

Fluoroquinolone and sulfonamide antibiotics (single and mixtures) impair the motor function of zebrafish larvae at environmentally relevant concentrations - Gleyson B. Castro; Juliano J. Corbi; Mateus Cottorello-Fonsêca; Daniela Correia; Demetrio Raldúa; David S. Alexandre; Thandy Junio da Silva Pinto; Eva Prats; Melissa Faria (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Glycosylation of chrysin with β-d-glucose tetraacetate (LQFM280) enhances its in vitro and in vivo neuroprotective effects against the toxicity induced by 3-nitropropionic acid - Robbert Mota Pereira; Hericles Mesquita Campos; Pâmela Yasmin de Oliveira Ferreira; Nkaa Uchenna; Yohanny Souza Silva; Victor Ifeanyi Okoh; Letizia Pruccoli; Evilanna Lima Arruda; Luciano Morais Lião; Pedro Augusto Alves Mota; Jacqueline Alves Leite; Raphaela de Castro Georg; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The genetic footprint of the European Roma diaspora: evidence from the Balkans to the Iberian Peninsula - Giacomo Francesco Ena; Aaron Giménez; Annabel Carballo-Mesa; Petra Lišková; Marcos Araújo Castro e Silva; David Comas (Human Genetics, 2025)
The Roma people have a complex demographic history shaped by their recent dispersal from a South Asian origin into Europe, accompanied by continuous population bottlenecks and gene flow. After settling in the Balkans around 1,000 years ago, the Roma gradually dispersed across Europe, and approximately 500 years ago, they established in the Iberian Peninsula what is now one of the largest Roma populations in Western Europe. Focusing specifically on the Iberian Roma, we conducted the most comprehensive genome-wide analysis of European Roma populations to date. Using allele frequency and haplotype-based methods, we analysed 181 individuals to investigate their genetic diversity, social dynamics, and migration histories at both continental and local scales. Our findings demonstrate significant gene flow from populations encountered during the Roma’s dispersal and confirm their South Asian origins. We show that, between the 14th and 19th centuries, the Roma spread westward from the Balkans in various waves, with multiple admixture events. Furthermore, our findings refute previous hypotheses of a North African dispersal route into Iberia and genetic connections to Jewish populations. The Iberian Roma exhibit ten times greater genetic differentiation compared to non-Roma Iberians, indicating significant regional substructure. Additionally, we provide the first genetic evidence of assortative mating within Roma groups, highlighting distinct mating patterns and suggesting a gradual shift towards increased integration with non-Roma individuals. This study significantly enhances our understanding of how demographic history and complex genetic structure have shaped the genetic diversity of Roma populations, while also highlighting the influence of their evolving social dynamics.

Dietary profiles of wild carnivores and Blastocystis occurrence: The case of the endangered Iberian lynx (Lynx pardinus) and systematic review - Javier Caballero-Gómez; Gabriel Ávalos; Pablo Matas-Méndez; Ana M. Figueiredo; Sabrina Castro-Scholten; Débora Jiménez-Martín; Pamela C. Köster; Mónica Santín; Begoña Bailo; David Cano-Terriza; Pedro Sarmento; Nuno Neves; et al. (Research in Veterinary Science, 2025)

Social life cycle assessment of drinking water: Tap water, bottled mineral water and tap water treated with domestic filters - Marianna Garfí; David Requejo-Castro; Cristina M. Villanueva (Environmental Impact Assessment Review, 2025)

Recovery after exploitation of stalked barnacles is facilitated by the presence of conspecifics: a study of post-harvest gap recolonization dynamics in SW Europe - Víctor Gómez-del Campo; Julio Arrontes; Teresa Cruz; Elsa Vázquez; Gonzalo Macho; Eric Thiébaut; Katja Geiger; Joana N. Fernandes; David Jacinto; Alba Aguión; Teresa Silva; David Mateus; et al. (Reviews in Fish Biology and Fisheries, 2025)
We have followed the recovery of gaps produced either by harvesters or by scientists in stands of stalked barnacle ( Pollicipes pollicipes ) during two years in four regions of Europe (SW Portugal, Galicia and Asturias in Spain and Brittany in France; n = 423 gaps), which was extended to four years in Asturias (n = 252 gaps). The presence of adult conspecifics in the margins of the gaps increased by at least four times the probability of initiation of their recovery. After two years of follow-up in the four regions, 90% of the gaps with adjacent conspecifics had initiated recolonization as opposed to only 60% in gaps with no adjacent adults. These figures remained stable after three years of follow up in Asturias, pointing to a large fraction of gaps which are recalcitrant to recolonization. Once initiated, the median rate of recovery after latency was 0.47 cm 2 /month in the four regions and 0.61 cm 2 /month in Asturias, increasing from 0.5 to 2.5 cm 2 /month for a 0 to 25 cm increase of perimeter in contact with adults, which is consistent with heavy recruitment on the stalks of conspecifics. The median estimated time to full recovery of gaps which initiated recovery was 2.65 years, thus recolonization is a slow process. Our results point to the main recommendations that a barnacle clump should never be removed entirely, so that the remaining adults serve as recruitment nuclei for the population, and that a maximum scraper width of 3.5 cm should be set to limit accessory capture of non-target individuals.

The role of photooxidation and organic matter in Cr(III) and Cr(VI) interactions with poly(lactic acid) microplastics in aqueous solution - Ricardo H.P. Pedroza; Calin David; José L. Barriada; Carlos Rey-Castro; Pablo Lodeiro (Science of The Total Environment, 2025)

Escherichia coli-associated granulomatous diseases in three cats - Milena C. Paz; Igor R. Santos; Lucas T. de Castro; Gabriela Hartmann; Luan C. Henker; Jacqueline Raiter; Regina T. Kemper; Júlia G. Wronski; Eryca C. Lamego; Luiza da Rosa Robusto; Luciana Sonne; David Driemeier; et al. (Journal of Comparative Pathology, 2025)

Effect of the co-substrate ratio on the anaerobic co-digestion of sewage sludge and the organic fraction of municipal solid waste at pilot scale - Carlos Esteven Pulgarín-Muñoz; Julio César Saldarriaga-Molina; Johan Camilo Castro-Valencia; Mauricio Andres Correa-Ochoa; Juan David Echeverry-Ruiz (International Biodeterioration & Biodegradation, 2025)

Paleoichthyology in the Philippines: A review of Cenozoic fish fossils with insights on its current status and future opportunities - Dominique Mediodia; Abigael Castro; Meyrick Tablizo; David Policarpio; Joeven Calvelo; John Phillip Baguio; Antero Borja; Chien-Hsiang Lin; Allan Gil Fernando (Geobios, 2025)

Distinct management units for the Critically Endangered angelshark (Squatina squatina) revealed in the Canary Islands - Eva K.M. Meyers; Nadia Faure; David Jiménez-Alvarado; Joanna Barker; Hector Toledo-Padilla; Fernando Tuya; Charlotte Pike; Lucy R. Mead; Michael J. Sealey; Maria Belén Caro; David M.P. Jacoby; Felipe Ravina Olivares; et al. (Conservation Genetics, 2025)
The angelshark, Squatina squatina , is listed as Critically Endangered on the IUCN Red List of Threatened Species, and remaining populations are highly fragmented throughout its historical distribution. The Canary Islands archipelago in the North East Atlantic has been identified as a uniquely large stronghold for the species. In the present study, we compared the population genetic structure of S. squatina across different islands of the Canary Island archipelago using both microsatellite and single nucleotide polymorphism (SNP) markers. Both markers revealed significant differentiation of angelsharks between islands in the archipelago, with three main genetic units at: (1) Tenerife, (2) Gran Canaria and (3) the island group consisting of La Graciosa, Lanzarote and Fuerteventura. Our results imply a connectivity barrier between some adjacent islands, most likely driven by abyssal depths, and varying geological history and formation of each island and oceanographic patterns (i.e. seasonal coastal upwellings off the African coast). Therefore, we suggest that in the Canary Islands, S. squatina populations should be managed locally, with conservation and research priorities designed and implemented specifically for each of the three genetic units.

Carbon stocks, technological development, and milk yields of dairy cattle silvopastoral production systems in the Andean-amazon region of Colombia - Henry Mavisoy; Edwin Castro Rincón; Adrian Rolando Riascos Vallejos; Juan Pablo Narváez-Herrera; Lorieth Rosas; Adriana del Socorro Guerra Acosta; Adrián Antonio Riascos Salcedo; Disney Magali Aguillon Alban; Carlos Chingal; André M. de Almeida; David Fangueiro (Agroforestry Systems, 2025)
This research aimed to assess carbon (C) stocks (living biomass, soil and detritus) in silvopastoral systems (SPS), the C density in living biomass (CLB) at the farm level, technological adoption and milk yields in an integrated fashion in small dairy farms in the Andean-Amazon region of Colombia. Technological adoption was assessed on a scale of 0 to 100% across 26 points. Milk yields from the top 10% highest-yielding farms were used for gap analysis. The lactation period and weaning age were considered as herd management variables. The study included 30 farms classified as high, medium or low SPS coverage. The average farm size was 9.1 ± 0.8 ha −1 where live fences (LF) and woodlots (WL) were the main SPS. The total C were 152.0 ± 13.8 Mg·ha- 1 , 152.2 ± 10.3 Mg·ha- 1 , and 73.2 ± 4.4 Mg·ha- 1 in WL, LF and pastures. Farms with high SPS coverage (10.8 ± 1.1%) presented a CLB density of 8.6 ± 2.0 Mg·ha −1 , 3.4 and 43 times higher than those with medium and low coverage, respectively. Average milk yield was 3190.1 ± 237.5 kg fat and protein-corrected milk (FPCM) cow −1 yr⁻ 1 , with the top 10% of farms having 6056.7 kg·FPCM·cow −1 yr⁻ 1 . Farms with low SPS coverage had the smallest yield gap (1221.4 ± 290 kg·FPCM·cow −1 yr⁻ 1 ) but also a lower average yield (2883.0 ± 290 kg·FPCM·cow⁻ 1 ·yr⁻ 1 ). The farms averaged 48.9 ± 2.1% in the technological adoption level, 271.5 ± 8.4 days of lactation period, and 129.3 ± 17.8 days of weaning age, with no significant differences across SPS levels. An integrated approach to jointly increase technology adoption, herd management, and the enhancement of SPS coverage at the farm level can reduce the yield gap while enhancing C stocks.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Multimodal packaging waste brand identification approach for extended producer responsibility traceability - Juan Carlos Arbeláez-Estrada; Jose Aguilar-Castro; Paola Vallejo-Correa; Daniel Correa; Santiago Ruiz-Arenas; Elizabeth Rendón-Vélez; David Ríos-Zapata; Joan Alvarado (Journal of Cleaner Production, 2025)

Assessment of SARS-CoV-2 exposure in exotic pets in Spain - David Cano-Terriza; Leira Fernández-Bastit; Júlia Vergara-Alert; Daniel B. Váquez-Calero; Sabrina Castro-Scholten; Javier Caballero-Gómez; Ignacio García-Bocanegra; Joaquim Segalés (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Optical immunosensor panel using quantum dot-antibody conjugates for highly sensitive detection of carbohydrate antigen 19–9 (CA19-9) - Daniela Oliveira; Pedro Oliveira; Ana Xu; Eduarda Rodrigues; Susana G. Guerreiro; Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ana Margarida L. Piloto (Analytica Chimica Acta, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Storylines of projected summer warming in Iberia using atmospheric circulation, soil moisture and sea surface temperature as drivers of uncertainty - Jose M. Garrido-Perez; David Barriopedro; Ricardo M. Trigo; Pedro M.M. Soares; Giuseppe Zappa; M. Carmen Álvarez-Castro; Ricardo García-Herrera (Atmospheric Research, 2024)

Harnessing the power of microalgae consortia for sustainable crop production: case study on lettuce (Lactuca sativa L.) - Luis Eduardo Díaz; Juan David Gonzalez; Maria Paula Morales-Gonzalez; Claudia L. Garzón-Castro (Journal of Applied Phycology, 2024)
Due to global food demand and need to protect the environment, improving crop productivity while reducing agrochemical use has become crucial. Microalgae offer a potential solution as they exhibit biostimulant and biofertilizer effects, improving both crop and soil quality. This study aimed to assess the impact of suspensions of freeze-dried Chlorella vulgaris (UTEX 265), Scenedesmus obliquus (UTEX 393), and Haematococcus pluvialis (UTEX 2505) biomass in distilled water on lettuce ( Lactuca sativa L.) germination and development. Different microalgae treatments, individually and mixtures, were applied. The study evaluated various plant growth parameters and the concentration of nutritional constituents, including reducing sugars, total polyphenols, antioxidant capacity, and chlorophyll a . In the first stage (germination), microalgae treatments ( C. vulgaris 2 g (CV2),; C vulgaris 0.66 g, S. obliquus 0.66 g and H. pluvialis 0.7 g (CV0.7:SO0.7:HP0.7) and C. vulgaris 1.5 g and S. obliquus 1.5 g (CV1.5:SO1.5) increased L. sativa seed germination rate and the number of germinated seeds. Significant changes were observed in growth-related variables such as height (CV0.7:SO9.7:HP0.7), stem diameter ( C. vulgaris 3 g (CV3)), root length ( S. obliquus 3 g (SO3)), and leaf area (CV1.5:SO1.5). In the second stage (plant development), microalgae treatments significantly increased dry weight from 2.71% (CV1.5:SO1.5) to 48.52% (SO3), reduced sugars from 3.20% (CV3) to 59.05% (CV1.5:SO1.5), total polyphenols from 7.99% (CV3) to 40.15% (CV1.5:SO1.5), antioxidant capacity from 0.77% (CV0.7:SO9.7:HP0.7) to 17.40% (CV1:HP1), and chlorophyll a from 23.01% (CV1.5:SO1.5) ( p ≤ 0.05). C. vulgaris and S. obliquus in blending were identified as the main microalgae promoting positive effects on L. sativa development. This study confirms that microalgae, particularly C. vulgaris and S. obliquus , can enhance crop quality, specifically in L. sativa . These findings demonstrate the potential of microalgae as biostimulants, supporting their application to improve crop productivity and emphasizing their role in sustainable agriculture.

Polymorphic pseudogenes in the human genome - a comprehensive assessment - Mónica Lopes-Marques; M. João Peixoto; David N. Cooper; M. João Prata; Luísa Azevedo; L. Filipe C. Castro (Human Genetics, 2024)
Background: Over the past decade, variations of the coding portion of the human genome have become increasingly evident. In this study, we focus on polymorphic pseudogenes, a unique and relatively unexplored type of pseudogene whose inactivating mutations have not yet been fixed in the human genome at the global population level. Thus, polymorphic pseudogenes are characterized by the presence in the population of both coding alleles and non-coding alleles originating from Loss-of-Function (LoF) mutations. These alleles can be found both in heterozygosity and in homozygosity in different human populations and thus represent pseudogenes that have not yet been fixed in the population. Results: A methodical cross-population analysis of 232 polymorphic pseudogenes, including 35 new examples, reveals that human olfactory signalling, drug metabolism and immunity are among the systems most impacted by the variable presence of LoF variants at high frequencies. Within this dataset, a total of 179 genes presented polymorphic LoF variants in all analysed populations. Transcriptome and proteome analysis confirmed that although these genes may harbour LoF alleles, when the coding allele is present, the gene remains active and can play a functional role in various metabolic pathways, including drug/xenobiotic metabolism and immunity. The observation that many polymorphic pseudogenes are members of multigene families argues that genetic redundancy may play a key role in compensating for the inactivation of one paralogue. Conclusions: The distribution, expression and integration of cellular/biological networks in relation to human polymorphic pseudogenes, provide novel insights into the architecture of the human genome and the dynamics of gene gain and loss with likely functional impact.

Absence of Crimean-Congo hemorrhagic fever virus in wild lagomorphs and their ticks in Spanish Mediterranean ecosystems - Sabrina Castro-Scholten; Javier Caballero-Gómez; Caroline Bost; David Cano-Terriza; Débora Jiménez-Martín; Martin H. Groschup; Mario Frías; Leonor Camacho-Sillero; Kerstin Fischer; Ignacio García-Bocanegra (Veterinary Microbiology, 2024)

Structural and functional alterations under stress conditions by contamination: A multi-species study in a non-forced multi-compartmented mesocosm - Mohammed Ariful Islam; David Salvatierra; María Pilar González; Andrea Cordero-de-Castro; Rajaa Kholssi; Ignacio Moreno-Garrido; Julián Blasco; Cristiano V.M. Araújo (Science of The Total Environment, 2024)

Anatomopathological characterization of hepatic lesions of feline infectious peritonitis in cats - Fernanda G. Cony; Vanessa C. Pereira; Mônica Slaviero; Rafael P. Lima; Lucas T. de Castro; José T.R. de Moraes; João M.G. Aliardi; David Driemeier; Luciana Sonne; Welden Panziera; Saulo P. Pavarini (Journal of Comparative Pathology, 2024)

Development and evaluation of hydraulic geometry relationships for large Brazilian river basins - Clívia Dias Coelho; Demetrius David da Silva; Michel Castro Moreira; Naziano Pantoja Filizola (Hydrological Sciences Journal, 2024)

Evolution of the transtensional Barreirinhas pull-apart system in the Brazilian Equatorial margin and its correlation with the African conjugate counterpart - David L. de Castro; Diógenes C. Oliveira; Francisco H.R. Bezerra (Tectonophysics, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cross-border surveillance of sheep and goat rabies in Brazil - Francisco Alyson Silva Oliveira; Rivanni Jeniffer Souza Castro; Abelardo Silva-Júnior; Raizza Eveline Escócio Pinheiro; Ricardo Antônio Pilegi Sfaciotte; David Germano Gonçalves Schwarz (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Periorbital necrotizing fasciitis: clinical perspectives on nine cases - David Oliver-Gutierrez; R. L. P. van der Veen; Elena Ros-Sánchez; Gloria Segura-Duch; Tirso Alonso; Alejandra Herranz-Cabarcos; Jessica Matas; Roberto Castro Seco; Miguel Ángel Arcediano; Miguel Ángel Zapata; Joan Oliveres (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Epidemiological survey and risk factors associated with Sarcoptes scabiei in wild lagomorphs in Spanish Mediterranean ecosystems - Sabrina Castro-Scholten; Ignacio García-Bocanegra; Natalia Iglesias; Rosa Casais; David Cano-Terriza; Débora Jiménez-Martín; Jesús Barbero-Moyano; Leonor Camacho-Sillero; Carlos Rouco; Javier Caballero-Gómez (Research in Veterinary Science, 2024)

Design and optimization of a strawberry-based dispersion to produce a spray drying functional powdered product, fortified with folic acid and zinc - Daniel Henao-González; Dairon David; Juan Torres-Oquendo; Paulo José do Amaral Sobral; Oscar Vega-Castro (Food and Bioproducts Processing, 2024)

Weak phylogenetic effect on specialist plant assemblages and their persistence on habitat islands - Adam Klimeš; Rafael Molina‐Venegas; Angelino Carta; Milan Chytrý; Luisa Conti; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; Francisco E. Méndez‐Castro; David Zelený; et al. (Journal of Biogeography, 2024)
Aim The influence of species phylogenetic relatedness on the formation of insular assemblages remains understudied in functional island biogeography, especially for terrestrial habitat islands (i.e. distinct habitat patches embedded in a matrix that differ in the prevailing environmental conditions). Here, we tested three eco‐evolutionary hypotheses: (1) functional specialization of species (i.e. specialism) is associated with phylogenetic clustering at the habitat archipelago scale, (2) such clustering increases with insularity at the habitat island scale and (3) traits indicative of effective local persistence strategies shape island specialism. Location Terrestrial habitat islands, Europe (Fens in the Western Carpathians, Outcrops in Moravia and Mountaintops in the Cantabrian Range). Taxon Angiosperms. Methods We assessed the phylogenetic relatedness of habitat specialists in three different archipelagos composed of terrestrial habitat islands based on phylogenetic signals and phylogenetic diversity (PD) measures. We estimated the effect of insularity on PD using linear models and the effect of persistence traits on specialism using phylogenetic logistic regressions. Results Our hypotheses were largely not supported. Outcrop and mountaintop specialist assemblages did not exhibit any phylogenetic structuring, whereas fen specialists were clustered at the archipelago scale. Therefore, insularity seems not to act as a selective force for phylogenetic structure, and ecologically important persistence traits do not operate as precursors of specialism. Main Conclusions Our results show that species phylogenetic relatedness plays a minor role in shaping habitat island specialist assemblages. Furthermore, the effects of phylogenetic relatedness on assemblages of island specialists are system and scale dependent. Finally, accounting for species' phylogenetic relatedness on persistence traits yielded results similar to previous studies, which corroborates the positive relationship between insularity and functional traits (indicative of enhanced plant persistence abilities with increasing within‐archipelago insularity).

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

In vitro propagation strategies of Puya chilensis as an alternative for obtaining new cysteine proteases - Inelvis Castro Cabrera; Karel Vives Hernández; Mariela Anahí Bruno; Walter David Obregón; Martha Hernández de la Torre (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Epidemiological surveillance of Leishmania infantum in wild lagomorphs in Spanish Mediterranean ecosystems - Jesús Barbero-Moyano; Sabrina Castro-Scholten; Moisés Gonzálvez; Inmaculada Moreno; Mercedes Domínguez; David Cano-Terriza; Débora Jiménez-Martín; Leonor Camacho-Sillero; Remigio Martínez; Ignacio García-Bocanegra (Preventive Veterinary Medicine, 2024)

Artificial intelligence in biocapacity and ecological footprint prediction in Latin America and the Caribbean - David van der Woude; Gilmer Yovani Castro Nieto; Maria Andreina Moros Ochoa; Carolina Llorente Portillo; Anderson Quintero (Environment, Development and Sustainability, 2024)

Development of a flow-cell bioreactor for immobilized sulfidogenic sludge characterization using electrochemical H2S microsensors - Rebeca Castro; Gemma Gabriel; David Gabriel; Xavier Gamisans; Xavier Guimerà (Chemosphere, 2024)

Influence of anthropogenic effects and climate variability on streamflow in a Brazilian tropical watershed - Guilherme Barbosa Reis; Demetrius David da Silva; Michel Castro Moreira; Elpídio Inácio Fernandes Filho; Micael de Souza Fraga; Roberto Avelino Cecílio; Sávio Augusto Rocha Pinheiro; Gabriel Rodrigues Arruda Pinto (Theoretical and Applied Climatology, 2024)

Evaluating the bioactivity and toxicity of Siparuna guianensis Aublet (Siparunaceae) leaf extracts in zebrafish - Maria de Fátima Santos; William Franco Carneiro; Bárbara do Carmo Rodrigues Virote; Kiara Cândido Duarte da Silva; Tassia Flavia Dias Castro; Aline Pereira Coli; Luis David Solis Murgas; Marcos Ferrante; Manuel Losada Gavilanes; Elisangela Elena Nunes Carvalho (Advances in Traditional Medicine, 2024)

Source identification from unperceived low-frequency noise emissions at a Madrid home - León José Azcárate de Castro; David Baeza-Moyano; Gastón Sanglier Contreras; Roberto Alonso González-Lezcano (Building and Environment, 2024)

Assessment of water stress impact on olive trees using an accurate determination of the endocarp development - Marta Sánchez-Piñero; Mireia Corell; Laura L. de Sosa; Alfonso Moriana; Noemí Medina-Zurita; Engracia Madejón; Ignacio Girón; Pedro Castro-Valdecantos; María José Martín-Palomo; David Pérez-López (Irrigation Science, 2024)
When considering deficit irrigation, the most resistant period to water stress in olive crops is during the pit hardening. However, the determination of this period and the impact that water stress has on its onset or duration have not been clearly established. The aim of this work is to describe the impact of water stress on three processes that determine fruit development: fruit growth, endocarp hardening, and oil accumulation. This experiment was conducted between 2021 and 2022, in a plot with olive trees that were 3 years old at the beginning of the experiment. The young trees were of cv Manzanilla de Sevilla and were planted in a 4 × 1.5 m frame. The treatments were: Control, irrigated close to what is considered the optimum level in which the water status of the crop ensures the absence of water stress; RDI, with a moderate stress during the pit hardening stage; Rainfed and Traditional Rainfed. This latter was included only in 2022 using a 7 × 5 m frame. Traditional Rainfed was included to compare with Rainfed, these were similar in the maximum level of water stress but not in the duration. The fruit growth, oil accumulation, and endocarp hardness were measured for a period of 2 years. The hardness curves fit accurately established Period II which was the one with the fast hardness increases. The water potential was measured periodically on leaves at midday, whereby the minimum and average potential and the stress integral were obtained for each of the periods indicated before using pit hardness measurements. The results suggest that endocarp hardening was the process most resistant to water stress, as it showed very little variation from the seasonal pattern, despite the high levels of stress achieved. The fruit growth process was the most sensitive to water stress, but the recovery was fast in conditions of moderate water stress level. The oil accumulation started slowly during Period II, but its rate increased at the end of the period. This later process was moderately resistant to water stress. However, although the accumulation rate was faster during Period III, it was influenced by the water status during Period II. Cumulative water stress was related with fruit growth and oil accumulation processes. Endocarp development could be useful for determining a/the deficit irrigation period because of its almost constant pattern. These periods would permit water management optimization according to final use of the fruit (oil or table). However, continuous monitoring of water stress would be needed.

Estimated evaporation of lakes by climate reanalysis data and artificial neural networks - Eduardo Morgan Uliana; Uilson Ricardo Venâncio Aires; Marionei Fomaca de Sousa Junior; Demetrius David da Silva; Michel Castro Moreira; Ibraim Fantin da Cruz; Handrey Borges Araujo (Journal of South American Earth Sciences, 2024)

Assessment of physical schemes for WRF model in convection-permitting mode over southern Iberian Peninsula - Feliciano Solano-Farias; Matilde García-Valdecasas Ojeda; David Donaire-Montaño; Juan José Rosa-Cánovas; Yolanda Castro-Díez; María Jesús Esteban-Parra; Sonia Raquel Gámiz-Fortis (Atmospheric Research, 2024)

R-phycoerythrin alginate/shellac beads by external gelation: Process optimization and the effects of gastrointestinal digestion for nutraceutical applications - Pablo Castro-Varela; Mónica Rubilar; Antonio Martínez-Férez; David Fuentes-Ríos; Juan Manuel López-Romero; Claudio Alarcón; Roberto Abdala-Díaz; Félix L. Figueroa (Algal Research, 2024)

Streamflow prediction based on machine learning models and rainfall estimated by remote sensing in the Brazilian Savanna and Amazon biomes transition - Marionei Fomaca de Sousa; Eduardo Morgan Uliana; Ricardo Venâncio Uilson Aires; Luis Miguel Castillo Rápalo; Demetrius David da Silva; Michel Castro Moreira; Luana Lisboa; Danielle da Silva Rondon (Modeling Earth Systems and Environment, 2024)

Feeding ecology of the African cuttlefish Sepia bertheloti (Cephalopoda: Sepiidae) in western Africa - Airam Guerra-Marrero; Ana Espino-Ruano; Lorena Couce-Montero; David Jiménez-Alvarado; José J. Castro (Fisheries Research, 2024)

Bayesian hierarchical modelling of the geospatial distribution of fasciolosis in dairy cattle and the impact on production: Application to the main milk-producing region (Galicia) in Spain - Marta González-Warleta; José Antonio Castro-Hermida; Mario Figueira; Jesúa López; David Conesa; Antonio López-Quílez; Florencio M. Ubeira; Mercedes Mezo (Veterinary Parasitology, 2024)

Interactions of humic acid with pristine poly (lactic acid) microplastics in aqueous solution - Ricardo H.P. Pedroza; Calin David; Pablo Lodeiro; Carlos Rey-Castro (Science of The Total Environment, 2024)

Occurrence of Anaplasma spp. in wild lagomorphs from Southern Spain: Molecular detection of new Anaplasma bovis lineages - Susana Remesar; Sabrina Castro-Scholten; Patrocinio Morrondo; Pablo Díaz; Débora Jiménez-Martín; Leonor Muñoz-Fernández; Tomás Fajardo; David Cano-Terriza; Ignacio García-Bocanegra (Research in Veterinary Science, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Pedotransfer functions and machine learning: Advancements and challenges in tropical soils - Lucas de Castro Moreira da Silva; Ricardo Santos Silva Amorim; Elpídio Inácio Fernandes Filho; Edwaldo Dias Bocuti; Demetrius David da Silva (Geoderma Regional, 2023)

Genome-wide association study reveals candidate genes for traits related to meat quality in Colombian Creole hair sheep - Herman Alberto Revelo; Diana López-Alvarez; Yineth Alexandra Palacios; Oscar David Vergara; Moris Bustamante Yánez; Manuel Fernando Ariza; Susan Lorena Castro Molina; Yurany Ortiz Sanchez; Luz Ángela Alvarez (Tropical Animal Health and Production, 2023)
Genome-wide association studies (GWAS) allow identifying genomic regions related to traits of economic importance in animals of zootechnical interest. The objective of this research was to conduct a genome-wide association study on meat quality traits using the Illumina OvineSNPs50 BeadChip array. The animals were sampled in the departments of Córdoba, Cesar, and Valle del Cauca. The genotypes obtained with the Illumina OvineSNP50 BeadChip microarray were analyzed SNP (single-nucleotide polymorphism) data to conduct a GWAS for pH and water-holding capacity (WHC) traits measured after 7 days of maturation, in the Longissimus dorsi (LD) muscle, in 167 Creole hair sheep of 12 months old belonging to Pelibuey (CHSP, n = 60), Ethiopian (CHSE, n = 44), and Sudan (CHSS, n = 63) breeds. The GWAS was done using a mixed linear model (MLMA) and based on the Ovis aries v3.1 genome. The CHSE showed the lowest meat juice release and, consequently, the highest water-holding capacity (WHC = 30.6 ± 0.1), suggesting that this breed has better performance in the meat industry compared with CHSS (WHC = 41.7 ± 0.1) and CHSP (WHC = 36.8 ± 0.1), since there is a relationship between WHC and juiciness. For the character pH, it was not possible to annotate genes related to meat quality, while, for the WHC, they have obtained 11 candidate genes associated (ELOVL2, ARAP2, LOC101102527, SHOC2, AIPL1, CSRNP3, IFRD, KDM8, NANS, DAPK1, IBN2, TPM2). Particularly, ELOVL2, ARAP2, IBN2, and TPM2 genes are involved in muscle contraction and fatty acid composition in sheep. In this study, we generated a baseline for GWAS related to meat quality traits in Colombian Creole hair sheep that can be used for future genomic selection plans.

Monitoring the dynamics of consumption of ungulate game by-products in vulture feeding stations in Iberian Mediterranean ecosystems - Moisés Gonzálvez; Jorge Paniagua; Débora Jiménez-Martín; David Cano-Terriza; Sabrina Castro-Scholten; Jesús Barbero-Moyano; Saúl Jiménez-Ruiz; Ignacio García-Bocanegra (Research in Veterinary Science, 2023)

From ground motion simulations to landslide occurrence prediction - Ashok Dahal; David Alejandro Castro-Cruz; Hakan Tanyaş; Islam Fadel; Paul Martin Mai; Mark van der Meijde; Cees van Westen; Raphaël Huser; Luigi Lombardo (Geomorphology, 2023)

A ratiometric carbon dots/AgInS2 quantum dots sensing probe for the kinetic determination of histamine resorting to N-PLS chemometric model - Rafael.C. Castro; Ricardo N.M.J. Páscoa; M.Lúcia M.F.S. Saraiva; Sara.C. Cunha; João L.M. Santos; David S.M. Ribeiro (Food Control, 2023)

Maximum stem diameter predicts liana population demography - Stefan A. Schnitzer; David M. DeFilippis; Antonio Aguilar; Boris Bernal; Salomé Peréz; Abelino Valdés; Seberino Valdés; Fidedigna Bernal; Adrián Mendoza; Biancolini Castro; Maria Garcia‐Leon (Ecology, 2023)
Determining population demographic rates is fundamental to understanding differences in species’ life‐history strategies and their capacity to coexist. Calculating demographic rates, however, is challenging and requires long‐term, large‐scale censuses. Body size may serve as a simple predictor of demographic rate; can it act as a proxy for demographic rate when those data are unavailable? We tested the hypothesis that maximum body size predicts species' demographic rate using repeated censuses of the 77 most common liana species on the Barro Colorado Island, Panama (BCI) 50‐ha plot. We found that maximum stem diameter does predict species' population turnover and demography. We also found that lianas on BCI can grow to the enormous diameter of 635 mm, indicating that they can store large amounts of carbon and compete intensely with tropical canopy trees. This study is the first to show that maximum stem diameter can predict plant species' demographic rates and that lianas can attain extremely large diameters. Understanding liana demography is particularly timely because lianas are increasing rapidly in many tropical forests, yet their species‐level population dynamics remain chronically understudied. Determining per‐species maximum liana diameters in additional forests will enable systematic comparative analyses of liana demography and potential influence across forest types.

Renal functional and structural alterations induced by intramuscular injection of Bothrops leucurus venom - Paloma Santos Hora; Joaquim Roque de Jesus Nogueira Junior; Ricardo David Couto; Leda Maria de Castro Coimbra Campos; Telma de Jesus Soares; Luciana Lyra Casais-e-Silva; Samira Itana de Souza (Toxicon, 2023)

Multi-level biological responses of Daphnia magna exposed to settleable atmospheric particulate matter from metallurgical industries - María Pilar González; Andrea Cordero-de-Castro; David Salvatierra; Rajaa Kholssi; Marisa Narciso Fernandes; Julián Blasco; Cristiano V.M. Araújo; Camilo Dias Seabra Pereira (Aquatic Toxicology, 2023)

Age, growth, and population structure of the African cuttlefish Sepia bertheloti based on beak microstructure - Airam Guerra-Marrero; Aurora Bartolomé; Lorena Couce-Montero; Ana Espino-Ruano; David Jiménez-Alvarado; José J. Castro; Catalina Perales-Raya (Marine Biology, 2023)
In this study, we explored the feasibility of using the beaks of the African cuttlefish Sepia bertheloti for age estimation and growth analysis. The rostrum sagittal section (RSS) of the lower beak was the most suitable region in the species. It was applied in samples caught off Morocco and Guinea-Bissau between June 2018 and January 2020. A maximum life expectancy of around 14 months was observed (specifically 419 days for cuttlefishes from Morocco and 433 from Guinea-Bissau). The males presented greater longevity, as the maximum age of the females was between 9 and 11 months. Sepia bertheloti showed a negative allometric growth; however, the exponential model better describes each population growth. By sexes, the males of both locations followed an asymptotic growth model while the females exhibited a non-asymptotic growth. The growth rates were different between locations, with the highest values in Guinea-Bissau. The males, in turn, grew faster for both study locations. In Guinea-Bissau, these growth differences were influenced by the hatching season since individuals born between autumn and winter were the fastest-growing. Samples from Morocco did not show growth differences between the hatching season and other seasons. These results indicate that the RSS of lower beaks are suitable for estimating the age, growth pattern, and population structure of Sepia bertheloti .

A continuous process in mixers-settlers for the removal/recovery of chromium in effluents from the tanning industry - Carlos Benito Martínez-Pérez; Zeferino Gamiño-Arroyo; Fernando Israel Gómez-Castro; Salvador Hernández; David Aarón Rodríguez-Alejandro; Lorena Eugenia Sánchez-Cadena; Alejandro Tadeo-Chávez; Agustín Ramón Uribe-Ramírez (Environmental Monitoring and Assessment, 2023)

Assessment, regionalization, and modeling rainfall erosivity over Brazil: Findings from a large national database - David Bruno de Sousa Teixeira; Roberto Avelino Cecílio; Michel Castro Moreira; Gabrielle Ferreira Pires; Elpídio Inácio Fernandes Filho (Science of The Total Environment, 2023)

In Silico Simulations and Functional Cell Studies Evidence Similar Potency and Distinct Binding of Pacific and Caribbean Ciguatoxins - Sandra Raposo-García; David Castro; Emilio Lence; Pablo Estévez; José Manuel Leão; Concepción González-Bello; Ana Gago-Martínez; M. Carmen Louzao; Carmen Vale; Luis M. Botana (Exposure and Health, 2023)
Ciguatoxins (CTX) cause ciguatera poisoning, which is the most common reported human food poisoning related to natural marine toxins. Pacific ciguatoxins are the most abundant and studied CTX analogues; however, the growing distribution of Caribbean analogues and the limited data available on their biological effects make necessary to re-evaluate their relative potency. For decades, the guidelines established by regulatory agencies have assumed that the potency of the Caribbean CTXs were tenfold lower than the Pacific CTXs. We present here an integrated study involving Neuro-2a cells (the method used worldwide to test ciguatoxins), electrophysiological assays, and in silico simulations that evidence the similar cytotoxicity of Caribbean and Pacific ciguatoxins and their asymmetry binding within sodium channels. The binding mode of the toxins was first explored by molecular docking using the GOLD program and the resulting binary complexes were further studied by Molecular Dynamics simulation studies using the molecular mechanics force field AMBER. The simulation studies explain their distinct impact on the activation potential of the channel as experimentally observed and provide a detailed picture of the effects caused by these toxins on an atomic scale. Graphical Abstract

Trend analysis and identification of possible periods of change in the occurrence of extreme streamflow events in a tropical basin - Carla Larissa Fonseca da Silva; Demetrius David da Silva; Michel Castro Moreira; Jackson Martins Rodrigues; Igor Steven de Sousa Rocha; Rafael Petruceli Coelho Lima; Arthur Telles Calegario (Journal of South American Earth Sciences, 2023)

Unraveling the sedimentation environment of Marajó island: Insights from geochemical studies and implications for the origin of potentially toxic element in soils - David Lukas de Arruda; João Carlos Ker; Carlos Ernesto Schaefer; Hidelblandi Farias de Melo; Danilo de Lima Camêlo; Ésio de Castro Paes; Saulo Henrique Barroso (Journal of South American Earth Sciences, 2023)

First record of partial albinism in the critically endangered Angelshark ( Squatina squatina ) (Linnaeus, 1758) - David Jimenez‐Alvarado; Eva Meyers; Airam Guerra‐Marrero; Ana Espino‐Ruano; Lorena Couce‐Montero; Joanna Barker; Michael Sealey; Héctor Toledo; Belén Caro; Charlotte Pike; David M.P. Jacoby; Lucy Mead; et al. (Journal of Fish Biology, 2023)
We report the first case of partial albinism in the Critically Endangered angelshark, Squatina squatina . The encounter with this specimen took place while SCUBA diving on the beach of Tufia, located on the east coast of the island of Gran Canaria on 2 April 2021. This is also the first confirmed finding of an albino elasmobranch specimen in the Canary Island archipelago.

Looking beyond Arthrospira: Comparison of antioxidant and anti-inflammatory properties of ten cyanobacteria strains - Patricia I. Gómez; Jaen Mayorga; David Flaig; Pablo Castro-Varela; Alejandra Jaupi; Pablo A. Ulloa; Jorge Soto-Bartierra; Vitalia Henríquez; Verónica Rojas (Algal Research, 2023)

Review of tectonic inversion of sedimentary basins in NE and N Brazil: Analysis of mechanisms, timing and effects on structures and relief - Francisco H. Bezerra; Fernando O. Marques; David L. Vasconcelos; Dilce F. Rossetti; Aline C. Tavares; Rubson P. Maia; David L. de Castro; Francisco C.C. Nogueira; Reinhardt A. Fuck; Walter E. Medeiros (Journal of South American Earth Sciences, 2023)

Biogeography of the spread of bluetongue disease in sheep in Brazil - Rivanni Jeniffer Souza Castro; Francisco Alyson Silva Oliveira; Taciana Galba da Silva Tenorio; Wagnner José Nascimento Porto; Maria Aparecida Scatamburlo Moreira; Maria José dos Santos Soares; Abelardo Silva-Júnior; David Germano Gonçalves Schwarz (Small Ruminant Research, 2023)

Authentication/discrimination, identification and quantification of cinnamon adulterants using NIR spectroscopy and different chemometric tools: A tutorial to deal with counterfeit samples - Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ricardo N.M.J. Páscoa (Food Control, 2023)

Novel clinical and immunological features associated with persistent post-acute sequelae of COVID-19 after six months of follow-up: a pilot study - Jiram Torres-Ruiz; Julieta Lomelín-Gascón; Jaquelin Lira Luna; Ana Sofia Vargas- Castro; Alfredo Pérez-Fragoso; Miroslava Nuñez-Aguirre; Beatriz Alcalá-Carmona; Abdiel Absalón-Aguilar; Jennifer T. Balderas-Miranda; José Luis Maravillas-Montero; Nancy R. Mejía-Domínguez; Carlos Núñez-Álvarez; et al. (Infectious Diseases, 2023)

Complementarity between mist-netting and low-cost acoustic recorders to sample bats in Amazonian rainforests and savannahs - William Douglas Carvalho; João David Miguel; Bruna da Silva Xavier; Adrià López-Baucells; Isaí Jorge de Castro; Renato Richard Hilário; José Júlio de Toledo; Ricardo Rocha; Jorge M. Palmeirim (Community Ecology, 2023)

A roadmap for the conservation of freshwater mussels in Europe - Ronaldo Sousa; Tadeusz Zając; Dariusz Halabowski; Olga V. Aksenova; Yulia V. Bespalaya; Francisco Carvalho; Paulo Castro; Karel Douda; Janine P. da Silva; Noé Ferreira‐Rodríguez; Juergen Geist; Clemens Gumpinger; et al. (Conservation Biology, 2023)
Europe has a long history of human pressure on freshwater ecosystems. As pressure continues to grow and new threats emerge, there is an urgent need for conservation of freshwater biodiversity and its ecosystem services. However, whilst some taxonomic groups, mainly vertebrates, have received a disproportionate amount of attention and funds, other groups remain largely off the public and scientific radar. Freshwater mussels (Bivalvia, Unionida) are an alarming example of this conservation bias and here we point out six conceptual areas that need immediate and long‐term attention: knowledge, threats, socioeconomics, conservation, governance and education. The proposed roadmap aims to advance research, policy and education by identifying the most pressing priorities for the short‐ and long‐term conservation of freshwater mussels across Europe.

Pathological Aspects and Immunohistochemical Evaluation of Troponin C in the Cardiovascular System of Dogs With Pheochromocytoma - Fernando F. Argenta; Mônica Slaviero; Lauren S. de Mello; Joanna V.Z. Echenique; Alexia A. Zorzan; Fernanda G. Cony; Marcele B. Bandinelli; Márcio B. de Castro; Saulo P. Pavarini; David Driemeier; Luciana Sonne (Topics in Companion Animal Medicine, 2023)

Predicting co-distribution patterns of parrots and woody plants under global changes: The case of the Lilac-crowned Amazon and Neotropical dry forests - María de Lourdes Nuñez Landa; Juan Carlos Montero Castro; Tiberio César Monterrubio-Rico; Sabina I. Lara-Cabrera; David A. Prieto-Torres (Journal for Nature Conservation, 2023)

Karstified zone interpretation using deep learning algorithms: Convolutional neural networks applications and model interpretability with explainable AI - Marcos V.G. Jacinto; Adrião D. Doria Neto; David L. de Castro; Francisco H.R. Bezerra (Computers & Geosciences, 2023)

Age validation in early stages of Sepia officinalis from beak microstructure - Airam Guerra-Marrero; Catalina Perales-Raya; Fedor Lishchenko; Ana Espino-Ruano; David Jiménez-Alvarado; Lorena Couce-Montero; José J. Castro (Marine Biology, 2023)
This is the first study addressing validation of the early growth stages (including the first increment) in the beaks of juvenile cuttlefishes. The age validation in juveniles of Sepia officinalis was performed by comparison of the number of increments observed in the rostrum surface of lower jaws with their true age. A total of 159 individuals were reared at 18 ºC and 21 ºC, with ages up to 31 days from hatching. The number of growth increments in the beak was counted and contrasted with the days of life after hatching, validating the hypothesis of one increment of growth corresponding to one day of life. The mean coefficient of variation between readings (measuring precision) was 2.95 ± 5.98%. The growth of the reading area (rostrum surface) and the periodicity of increment deposition showed no difference between the two culture temperatures and therefore daily deposition was confirmed at these temperatures.

Use of modeling to map potentially toxic elements and assess the risk to human health in soils affected by mining activity - Ésio de Castro Paes; Gustavo Vieira Veloso; David Lukas de Arruda Silva; Elpídio Inácio Fernandes-Filho; Maurício Paulo Ferreira Fontes; Emanuelle Mercês Barros Soares (CATENA, 2023)

Historical relationships of the Mesoamerican highlands, with emphasis on tropical montane cloud forests: a temporal cladistic biogeographical analysis - Marisol Castro-Torreblanca; David Espinosa; Alfredo Bueno-Hernández; Isolda Luna-Vega (Journal of Mountain Science, 2023)

250-Year reconstruction of pollarding events reveals sharp management changes in Iberian ash woodlands - David Candel-Pérez; Héctor Hernández-Alonso; Federico Castro; Gabriel Sangüesa-Barreda; Sven Mutke; Miguel García-Hidalgo; Vicente Rozas; José Miguel Olano (Trees, 2022)
Key message Tree-ring growth of pollarded narrow-leaved ash trees in Central Spain reveals traditional management cessation in 1970 and property-specific management patterns. Abstract Tree pollarding was a dominant management strategy of European forests for centuries creating open agroforestry landscapes with important cultural and environmental values. This traditional practice has been widely abandoned in last decades with a subsequent impact in terms of biodiversity and cultural loss. Central Spain hosts the largest and best-preserved area of pollarded narrow-leaved ash ( Fraxinus angustifolia Vahl.) woodlands in Europe. The main aim of this research is to obtain rigorous historical records of pollarding frequency to get adequate information for traditional ash management. We used dendrochronological techniques to evaluate temporal changes of pollarding frequency and rotation length. We analysed the stand level synchrony and the effect of land property on pollarding activity from 322 trees growing in eight pollard stands in Central Spain. Pollarding events were unequivocally identified at tree level by a characteristic change in growth pattern. We identified 2426 tree-level pruning events with the first event dated in 1777. Historical pruning recurrence ranged between 5 and 10 years with higher pollarding frequency on private lands. Pruning events within each site were synchronous, suggesting the existence of a rotational schema within each stand. Pruning frequency decreased drastically in the 1970s matching with the depopulation of rural areas and the general abandonment of traditional practices. Pollarding practices have recovered in recent decades although with lower intensity and lacking the synchronic historical patterns. Providing technical and economic support to make this traditional activity profitably would have strong environmental revenue due the multiple ecosystem services provided by pollarded ashes.

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Age and Sexual Maturity Estimation of Stranded Striped Dolphins, Stenella coeruleoalba, Infected with Brucella ceti - Karol Roca-Monge; Rocío González-Barrientos; Marcela Suárez-Esquivel; José David Palacios-Alfaro; Laura Castro-Ramírez; Mauricio Jiménez-Soto; Minor Cordero-Chavarría; Daniel García-Párraga; Ashley Barratclough; Edgardo Moreno; Gabriela Hernández-Mora (Oceans, 2022)
Age parameters in cetaceans allow examining conservation and studying individuals with growth affection. The age and sexual maturity of 51 stranded Stenella coeruleoalba striped dolphins from the Eastern Tropical Pacific (ETP) of Costa Rica, most suffering brucellosis (95.6%), were assessed. In order to ascertain the dolphins’ ages, we measured the length and growth of dentin-layer group counts (GLGs) and assessed flipper bone radiography without (FBSA) and with a formula (FBF). Sexual maturity was determined through gonadal histology and sexual hormone serum levels. Compared with a model based on S. coeruleoalba ages estimations in other latitudes, the striped dolphin studied displayed deficient growth parameters, with considerable variability in length, teeth, and flippers bone development. Close to 43% (n = 15) of GLGs’ measurements were below the body length average ranges for the predicted age, suggesting developmental abnormalities. Likewise, 34.4% and 31.2% of the dolphins assessed by FBSA and FBF were also below the body length based on age prediction curves, also indicating developmental abnormalities. This information is supported by the poor correlation between GLGs, FBSA, and FBF. Inconsistencies between sexually mature males and females related to GLGs, FBSA, and FBF were evident. Although the different oceanic settings of the ETP, such as contamination, food access, diseases, and other parameters, may influence size variation, our data also suggest that long-lasting debilitating brucellosis may account for detrimental growth in the ETP striped dolphins. Our study highlights the possible deleterious consequences of chronic infectious diseases in the cetacean populations already confronting distressful conditions.

Metagenomic next-generation sequencing restores the diagnosis of a rare infectious complication of B cell depletion - Margaux Garzaro; Lin-Pierre Zhao; Nathalie De Castro; Séverine Mercier-Delarue; Francois Camelena; Sabine Pereyre; Marie Gardette; Béatrice Berçot; Marion Malphettes; Cécile Bébéar; Jean-David Bouaziz; Jérôme Le Goff; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Cryopreservation of semen in streaked prochilod (Prochilodus lineatus): use of ultra-freezer as alternative technique to liquid nitrogen - Daniella Aparecida de Jesus Paula; Naiara Melo; William Franco Carneiro; Pedro Leite de Castro Uzeda; Bruna Resende Chaves; Isaac Filipe Moreira Konig; Luis David Solis Murgas (Aquaculture International, 2022)

The Technical and Economic Feasibility of the CENTEC Floating Offshore Wind Platform - Almudena Filgueira-Vizoso; Laura Castro-Santos; David Cordal Iglesias; Félix Puime-Guillén; Isabel Lamas-Galdo; Ana Isabel García-Diez; Emre Uzunoglu; Hugo Díaz; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
This paper defines a methodology for the economic feasibility analysis of a floating offshore wind farm composed of tensioned leg platforms, which are part of the EU ARCWIND research project. In this context, the phases and subphases of its life-cycle process are considered to deal with aspects such as bathymetry, characteristics of the platforms, distance from the farm to shore, distance from the farm to port and offshore wind speed. All the costs and other external parameters such as capital cost, electric tariff, interest rate, percentage of financing and corporate tax have been analysed to calculate the internal rate of return, net present value, discounted pay-back period and levelized cost of energy of the farm. This work studies a farm composed of TLP offshore wind platforms designed by CENTEC and located at Ribadeo in Spain. Results indicate the costs and the economic feasibility of this platform for deep waters. They indicate that the platform is economically feasible for the location selected.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Preparation of Ciguatoxin Reference Materials from Canary Islands (Spain) and Madeira Archipelago (Portugal) Fish - David Castro; Pablo Estévez; José Manuel Leao-Martins; Robert W. Dickey; Natalia García-Álvarez; Fernando Real; Pedro Reis Costa; Ana Gago-Martínez (Journal of Marine Science and Engineering, 2022)
Ciguatoxins (CTXs) are naturally occurring neurotoxins that can accumulate in fish and cause Ciguatera Poisoning (CP) in seafood consumers. Ciguatoxic fish have been detected in tropical and subtropical regions of the world including the Pacific and Indian Oceans, the Caribbean Sea, and more recently in the northeast Atlantic Ocean. The biogeographic distribution of ciguatoxic fish appears to be expanding; however, the paucity of CTX standards and reference materials limits the ability of public health authorities to monitor for these toxins in seafood supply chains. Recent reports establish that Caribbean Ciguatoxin-1 (C-CTX1) is the principal toxin responsible for CP cases and outbreaks in the northeast Atlantic Ocean and that C-CTX congener profiles in contaminated fish samples match those from the Caribbean Sea. Therefore, in this work, C-CTX reference materials were prepared from fish obtained from the northeast Atlantic Ocean. The collection of fish specimens (e.g., amberjack, grouper, or snapper) was screened for CTX-like toxicity using the in vitro sodium channel mouse neuroblastoma cytotoxicity assay (N2a cell assay). Muscle and liver tissues from toxic specimens were pooled for extraction and purified products were ultimately profiled and quantified by comparison with authentic C-CTX1 using LC-MS/MS. This work presents a detailed protocol for the preparation of purified C-CTX reference materials to enable continued research and monitoring of the ciguatera public health hazard. To carry out this work, C-CTX1 was isolated and purified from fish muscle and liver tissues obtained from the Canary Islands (Spain) and Madeira archipelago (Portugal).

Crustal Thermal Structure of the Brazilian Equatorial Margin Using Fourier and Continuous Wavelet Transforms: A Comparative Analysis Based on Different Magnetic Datasets - Duvan Ricardo Herrera Herrera; David Lopes de Castro; Jefferson Tavares Cruz Oliveira; Diógenes Custódio de Oliveira (Surveys in Geophysics, 2022)

Monitoring SARS-CoV-2 in the Wastewater and Rivers of Tapachula, a Migratory Hub in Southern Mexico - Eugenia Zarza; Elia Diego-García; Luz Verónica García; Ricardo Castro; Gamaliel Mejía; David Herrera; Raúl Cuevas; Ángeles Palomeque; Pavel Iša; Karina Guillén (Food and Environmental Virology, 2022)

A large-scale comparison of reproduction and recruitment of the stalked barnacle Pollicipes pollicipes across Europe - Alba Aguión; Teresa Cruz; José Luis Acuña; Caroline Broudin; João J. Castro; Dominique Davoult; Jesus Dubert; Joana N. Fernandes; Katja J. Geiger; David Jacinto; David Mateus; Carlota Muñiz; et al. (Marine Biology, 2022)
Understanding large-scale spatial and temporal patterns of marine populations is a central goal in ecology, which has received renewed attention under climate change. However, few studies explore the large-scale dynamics of populations using standardized protocols and during the same time frames. We studied the phenology and intensity of reproduction and recruitment for the intertidal stalked barnacle Pollicipes pollicipes over an European scale and described their potential linkages with environmental variables. This species supports profitable fisheries in the Iberian Peninsula (Spain and Portugal). In Brittany (France), we had observed a significant lower reproductive effort (long non-breeding season, short breeding period in summer) and low values of recruitment intensity. This pattern may be related to the fact that Brittany corresponds to the northern limit of the distribution of this species in continental Europe. On the Iberian Peninsula, the most different region was Galicia (Spain), with Asturias (Spain) and SW Portugal being more similar. In Galicia, we have observed a contradictory pattern characterized by the absence of a non-breeding period and by a shorter recruitment season than observed in other Iberian regions. Our results suggest that air temperature, SST and chlorophyll-a might be related to the variability in reproduction and recruitment patterns of P. pollicipes . Moreover, spring and early summer upwelling in SW Portugal and Galicia might be inhibiting recruitment in this period. At the northern limit, the expected increase in performance under climate change might facilitate the recovery of populations after exploitation, increasing the resilience of the resource to fishing pressure.

Ambio fit for the 2020s - Erik Andersson; Wiebren J. Boonstra; Maricela de la Torre Castro; Alice C. Hughes; Ulrik Ilstedt; Arne Jernelöv; Bengt-Gunnar Jonsson; Zahra Kalantari; Carina Keskitalo; Emma Kritzberg; Thomas Kätterer; Jeffrey A. McNeely; et al. (Ambio, 2022)

Detecting the attack of the fall armyworm (Spodoptera frugiperda) in cotton plants with machine learning and spectral measurements - Ana Paula Marques Ramos; Felipe David Georges Gomes; Mayara Maezano Faita Pinheiro; Danielle Elis Garcia Furuya; Wesley Nunes Gonçalvez; José Marcato Junior; Mirian Fernandes Furtado Michereff; Maria Carolina Blassioli-Moraes; Miguel Borges; Raúl Alberto Alaumann; Veraldo Liesenberg; Lúcio André de Castro Jorge; et al. (Precision Agriculture, 2022)

Insularity promotes plant persistence strategies in edaphic island systems - Luisa Conti; Francisco E. Méndez‐Castro; Milan Chytrý; Lars Götzenberger; Michal Hájek; Michal Horsák; Borja Jiménez‐Alfaro; Jitka Klimešová; David Zelený; Gianluigi Ottaviani (Global Ecology and Biogeography, 2022)
Aim Trait‐based approaches are being used increasingly in island biogeography, providing key insights into the eco‐evolutionary dynamics of insular systems. However, the determinants of persistence of plant species after they have arrived and established on an island remain largely unexplored. Here, we used three edaphic island systems (i.e., habitat patches distinguished from the landscape matrix by distinct soil conditions and specialized vegetation) to examine relationships between persistence strategies (those associated with clonality, bud bank, seed mass and life‐form) and insularity. We hypothesized that insularity promotes and selects strategies to persist locally, such that species occurring on small and/or isolated edaphic islands show trait values indicative of enhanced persistence and lower functional diversity. Location Three European systems of edaphic islands in the Western Carpathians, Moravia and the Cantabrian Range. Time period Present. Major taxa studied Vascular plants. Methods For each system, we used linear models to explore persistence‐related plant trait patterns (mean trait values and functional diversity) in relationship to three insularity metrics (island size, isolation and target effect). We focused on patterns of edaphic island specialists because their presence is confined to the islands. Results We found that insularity metrics largely explained the variation of the mean value and diversity of persistence‐related traits of edaphic island plant specialists. Specifically, insularity was positively related to traits supporting local persistence (e.g., more extensive lateral spread) and to a reduced variability in persistence traits. More insular systems showed stronger and more numerous trait–insularity links. Main conclusions Insularity can affect plant species diversity, form and function in edaphic island systems, such as selecting for enhanced and less diverse persistence strategies. Plant species occurring in insular systems might therefore avoid or delay local extinction by promoting adaptive strategies to persist in situ .

Projected changes in the season of hot days in the Middle East and North Africa - Rubén Varela; Laura Rodríguez‐Díaz; David Barriopedro; Maite de Castro; Xurxo Costoya; Ricardo García‐Herrera; Moncho Gómez‐Gesteira (International Journal of Climatology, 2022)
The present study analyses changes in the timing and duration of the hot days season over the Middle East and North Africa region from 1970 to 2099 using model simulations of 11 regional models from the Coordinated Regional Climate Downscaling Experiment under the RCP8.5 scenario. In general, a non‐symmetrical lengthening of the hot days season is projected, with a tendency to extend more into spring than into autumn. By the end of the century and the RCP8.5 scenario, Western Africa and the Persian Gulf display a hot days season starting 60 days earlier than in the historical period (1970–1999) (May vs. July, respectively). Southernmost latitudes are the most affected by a later retreat of the hot days season, of up to 60 days with respect to the historical period (October vs. August). The length of the extreme season is projected to increase between 100 and 120 days for the southernmost latitudes and the Persian Gulf resulting in nearly four more months with hot days conditions.

Ranking the direct threats to biodiversity in sub-Saharan Africa - Craig Leisher; Nathaniel Robinson; Matthew Brown; Deo Kujirakwinja; Mauricio Castro Schmitz; Michelle Wieland; David Wilkie (Biodiversity and Conservation, 2022)
Sub-Saharan Africa receives large investments in biodiversity conservation, and if these investments can be concentrated on the highest threats to biodiversity, the benefits to conservation from the investments would increase. Yet there is no available prioritization of the many direct threats to biodiversity to inform organizations developing sub-Saharan or sub-regional conservation strategies. Consequently, regional investments by funders of biodiversity conservation such as international conservation organizations, foundations, and bilateral and multilateral donors may be suboptimal. The objective of this study was to determine what are the highest direct threats to biodiversity in sub-Saharan Africa and its sub-regions. To do this, we collected threat data using standardized IUCN threat categories from a Delphi consensus of sub-Saharan Africa biodiversity experts, known threats to IUCN Red-listed sub-Saharan African species, and National Biodiversity Strategy and Action Plans from 40 sub-Saharan African countries. After averaging the threat ranking from the three sources, the highest threats were: (1) annual and perennial crops (non-timber); (2) fishing and harvesting aquatic resources in marine and freshwater areas; (3) logging and wood harvesting in natural forests; and (4) hunting and collecting terrestrial animals. The highest-ranked sub-regional threats were hunting in Central Africa and agriculture in East Africa, Southern Africa, and West Africa. Aligning biodiversity investments to address these threats and tailoring activities to reflect local socio-ecological contexts would increase the conservation of biodiversity in sub-Saharan Africa.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evaluation of air pollution tolerance index and anticipated performance index of six plant species, in an urban tropical valley: Medellin, Colombia - Mauricio Correa-Ochoa; Juliana Mejia-Sepulveda; Julio Saldarriaga-Molina; Camilo Castro-Jiménez; David Aguiar-Gil (Environmental Science and Pollution Research, 2022)

Insulin and glucose regulation at rest and during flight in a Neotropical nectar-feeding bat - David Leonardo Justinico Castro; Renata Maria P. Freitas; Stella Bicalho Silva; Fabiana Cristina Silveira Alves de Melo; Mariaurea M. Sarandy; Esteban Giraldo Ospina; Sirlene Rodrigues Sartori; Reggiani Vilela Gonçalves; Mariella Bontempo Freitas (Mammalian Biology, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

Genome size variation in Cactaceae and its relationship with invasiveness and seed traits - Sara Lopes; Lucie Mota; Mariana Castro; Gabrielle Nobre; Ana Novoa; David M. Richardson; João Loureiro; Sílvia Castro (Biological Invasions, 2021)

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS - Irina S. Moreira; Alexandre Lebel; Xianzhi Peng; Paula M. L. Castro; David Gonçalves (Biodegradation, 2021)

Adenosine A2A receptor null chondrocyte transcriptome resembles that of human osteoarthritic chondrocytes - Cristina M. Castro; Carmen Corciulo; Benjamin Friedman; Zhi Li; Samson Jacob; David Fenyo; Bruce N. Cronstein (Purinergic Signalling, 2021)

High-fidelity broadband prediction of regional seismic response: a hybrid coupling of physics-based synthetic simulation and empirical Green functions - David Castro-Cruz; Filippo Gatti; Fernando Lopez-Caballero (Natural Hazards, 2021)

Detection of porcine circovirus type 2 (PCV2) in the Philippines and the complexity of PCV2-associated disease diagnosis - Agnes dela Cruz; Chiara Palmieri; Rachel Azul; Christina Legaspi; Suzan Lola; Tamsin S. Barnes; Christopher R. Parke; Conny Turni; John I. Alawneh; Augusto S. Baluyut; Voltaire G. Basinang; Jose E. David; et al. (Tropical Animal Health and Production, 2021)

GABAergic deficits in absence of LPA1 receptor, associated anxiety-like and coping behaviors, and amelioration by interneuron precursor transplants into the dorsal hippocampus - Cristina Rosell-Valle; Magdalena Martínez-Losa; Elisa Matas-Rico; Estela Castilla-Ortega; Emma Zambrana-Infantes; Ana Isabel Gómez-Conde; Lourdes Sánchez-Salido; David Ladrón de Guevara-Miranda; Carmen Pedraza; Pedro Jesús Serrano-Castro; Jerold Chun; Fernando Rodríguez de Fonseca; et al. (Brain Structure and Function, 2021)

Ten years of monitoring recruitment of the edible stalked barnacle Pollicipes pollicipes : linking to oceanographic variability - Joana Nascimento Fernandes; David Jacinto; Nélia Penteado; Alina Sousa; David Mateus; Maria Inês Seabra; Teresa Silva; Paola Castellanos; João José Castro; Teresa Cruz (Limnology and Oceanography, 2021)
Understanding recruitment patterns of an exploited species is essential to predict changes in population dynamics and to improve its management and conservation. Temporal variability in recruitment of the edible stalked barnacle Pollicipes pollicipes was analyzed over a decade (consecutive annual recruitment seasons from 2007 to 2016) at a cape area located in the Canary‐Iberia Current Upwelling System (Cape of Sines, Southwestern Portugal), in terms of (1) the timing and length of the main recruitment season and (2) the variation in monthly and annual recruitment intensity and its relationship with several oceanographic variables. A longer recruitment season was detected, corresponding to approximately 9–10 months (June through either March or April of the following year, as in 2012, 2015, and 2016) in recent years, while a shorter recruitment season was detected between 2007 and 2010 ( −1 ) than in the first 5 yr of the 10‐yr period (ca. 12 recruits adult −1 ). Correlation analyses between monthly recruitment and oceanographic variables revealed a significant positive correlation with sea surface temperature and a negative correlation with upwelling index. Results indicate a trend toward a longer recruitment season and a higher recruitment intensity in recent years (2012–2016), and a clear association between recruitment of P. pollicipes and both relaxation of upwelling and seawater warming.

Modelling surface water dynamics in an Amazonian sub-basin: impacts of hydraulic geometry refinement - Clívia Dias Coelho; Demetrius David da Silva; Michel Castro Moreira; Naziano Pantoja Filizola; Ayan Fleischmann (Hydrological Sciences Journal, 2021)

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Nosocomial infections associated to COVID-19 in the intensive care unit: clinical characteristics and outcome - Tommaso Bardi; Vicente Pintado; Maria Gomez-Rojo; Rosa Escudero-Sanchez; Amal Azzam Lopez; Yolanda Diez-Remesal; Nilda Martinez Castro; Patricia Ruiz-Garbajosa; David Pestaña (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Epidemiological surveillance of chikungunya fever in Mexico since its introduction in 2014–2016 and identification of circulating genotypes - Belem Torres-Longoria; David Esaú Fragoso-Fonseca; Alma Núñez-León; María de la Luz Torres; Mauricio Vázquez-Pichardo; Noé Escobar-Escamilla; Claudia Wong-Arámbula; José Ernesto Ramírez-González; Alfonso Méndez-Tenorio; María Eugenia Castro-Mussot; María M. B. Moreno-Altamirano; Jorge Membrillo-Hernández; et al. (Molecular Biology Reports, 2021)

Estimation of suspended sediment concentration in Guamá River in the Amazon region - Pablo Abreu de Oliveira; Claudio José Cavalcante Blanco; André Luiz Amarante Mesquita; David Franco Lopes; Manoel Domingos Castro Furtado Filho (Environmental Monitoring and Assessment, 2021)

Seismic stratigraphy of a deep water basin in the Brazilian equatorial margin: the eastern portion of Potiguar Basin and Touros High - Júlia C. L. G. Fonseca; Helenice Vital; Yoe A. R. Perez; David L. Castro; André G. Aquino da Silva; Moab P. Gomes (Geo-Marine Letters, 2020)

Framework for Development of an Economic Analysis Tool for Floating Concrete Offshore Wind Platforms - David Cordal-Iglesias; Almudena Filgueira-Vizoso; Eugenio Baita-Saavedra; Manuel Ángel Graña-López; Laura Castro-Santos (Journal of Marine Science and Engineering, 2020)
The objective of this work is to establish a framework for the development of an economic analysis tool for floating offshore wind platforms built in concrete. The operation and usefulness of the beta version of a software, called Arcwind, is explained. It calculates the main economic aspects of offshore wind platforms built in concrete considering different locations in the European Atlantic Arc. This software allows the user to select different input parameters such as: the type of platform, the installation area of the farm, its specific location and in this way create different analysis scenarios. This paper analyzes the case study to install TELWIND® offshore concrete floating platforms in the Canary Islands, in Spain. The software provides data on the main economic parameters of the farm, such as Levelized Cost Of Energy (LCOE), Net Present Value (NPV), Internal Rate of Return (IRR), Pay-Back Period (PBP), as well as the main costs: cost of conception and definition, cost of design and development, cost of manufacturing, cost of installation, cost of operation and cost of dismantling. Using these parameters, a first analysis of the viability of this type of floating technology built on concrete is shown.

Hydropower impact on the river flow of a humid regional climate - Julian David Hunt; Giacomo Falchetta; Behnam Zakeri; Andreas Nascimento; Paulo Smith Schneider; Natália Assis Brasil Weber; André Luiz Amarante Mesquita; Paulo Sergio Franco Barbosa; Nivalde José de Castro (Climatic Change, 2020)
Land use and water management have considerable impacts on regional climates. This paper proposes that in humid regions with low wind patterns the construction of hydropower storage reservoirs contributes to the increases in the probability of precipitation in the regional climate. This observation has been tested with a methodology that calculates the cumulative influence of reservoir construction in the basins surrounding with a proposed index named Cumulative Impact of Existing Reservoirs, and compares this index with the historical flow of the rivers. It was found that the construction of reservoirs in Brazil had a considerable impact on its river flows.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

5 km front crawl in pool and open water swimming: breath-by-breath energy expenditure and kinematic analysis - Rodrigo Zacca; Vânia Neves; Tiago da Silva Oliveira; Susana Soares; Luís Manuel Pinto Lopes Rama; Flávio Antônio de Souza Castro; João Paulo Vilas-Boas; David B. Pyne; Ricardo J. Fernandes (European Journal of Applied Physiology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Coral reef resilience to thermal stress in the Eastern Tropical Pacific - Mauricio Romero‐Torres; Alberto Acosta; Ana M. Palacio‐Castro; Eric A. Treml; Fernando A. Zapata; David A. Paz‐García; James W. Porter (Global Change Biology, 2020)
Coral reefs worldwide are threatened by thermal stress caused by climate change. Especially devastating periods of coral loss frequently occur during El Niño‐Southern Oscillation (ENSO) events originating in the Eastern Tropical Pacific (ETP). El Niño‐induced thermal stress is considered the primary threat to ETP coral reefs. An increase in the frequency and intensity of ENSO events predicted in the coming decades threatens a pan‐tropical collapse of coral reefs. During the 1982–1983 El Niño, most reefs in the Galapagos Islands collapsed, and many more in the region were decimated by massive coral bleaching and mortality. However, after repeated thermal stress disturbances, such as those caused by the 1997–1998 El Niño, ETP corals reefs have demonstrated regional persistence and resiliency. Using a 44 year dataset (1970–2014) of live coral cover from the ETP, we assess whether ETP reefs exhibit the same decline as seen globally for other reefs. Also, we compare the ETP live coral cover rate of change with data from the maximum Degree Heating Weeks experienced by these reefs to assess the role of thermal stress on coral reef survival. We find that during the period 1970–2014, ETP coral cover exhibited temporary reductions following major ENSO events, but no overall decline. Further, we find that ETP reef recovery patterns allow coral to persist under these El Niño‐stressed conditions, often recovering from these events in 10–15 years. Accumulative heat stress explains 31% of the overall annual rate of change of living coral cover in the ETP. This suggests that ETP coral reefs have adapted to thermal extremes to date, and may have the ability to adapt to near‐term future climate‐change thermal anomalies. These findings for ETP reef resilience may provide general insights for the future of coral reef survival and recovery elsewhere under intensifying El Niño scenarios.

The Use of the Normalized Difference Vegetation Index to Analyze the Influence of Vegetation Cover Changes on the Streamflow in the Manhuaçu River Basin, Brazil - Uilson Ricardo Venâncio Aires; Demetrius David da Silva; Michel Castro Moreira; Carlos Antônio Alvares Soares Ribeiro; Celso Bandeira de Melo Ribeiro (Water Resources Management, 2020)

Accounting for multiple ecosystem services in a simulation of land‐use decisions: Does it reduce tropical deforestation? - Thomas Knoke; Carola Paul; Anja Rammig; Elizabeth Gosling; Patrick Hildebrandt; Fabian Härtl; Thorsten Peters; Michael Richter; Karl‐Heinz Diertl; Luz Maria Castro; Baltazar Calvas; Santiago Ochoa; et al. (Global Change Biology, 2020)
Conversion of tropical forests is among the primary causes of global environmental change. The loss of their important environmental services has prompted calls to integrate ecosystem services (ES) in addition to socio‐economic objectives in decision‐making. To test the effect of accounting for both ES and socio‐economic objectives in land‐use decisions, we develop a new dynamic approach to model deforestation scenarios for tropical mountain forests. We integrate multi‐objective optimization of land allocation with an innovative approach to consider uncertainty spaces for each objective. These uncertainty spaces account for potential variability among decision‐makers, who may have different expectations about the future. When optimizing only socio‐economic objectives, the model continues the past trend in deforestation (1975–2015) in the projected land‐use allocation (2015–2070). Based on indicators for biomass production, carbon storage, climate and water regulation, and soil quality, we show that considering multiple ES in addition to the socio‐economic objectives has heterogeneous effects on land‐use allocation. It saves some natural forest if the natural forest share is below 38%, and can stop deforestation once the natural forest share drops below 10%. For landscapes with high shares of forest (38%–80% in our study), accounting for multiple ES under high uncertainty of their indicators may, however, accelerate deforestation. For such multifunctional landscapes, two main effects prevail: (a) accelerated expansion of diversified non‐natural areas to elevate the levels of the indicators and (b) increased landscape diversification to maintain multiple ES, reducing the proportion of natural forest. Only when accounting for vascular plant species richness as an explicit objective in the optimization, deforestation was consistently reduced. Aiming for multifunctional landscapes may therefore conflict with the aim of reducing deforestation, which we can quantify here for the first time. Our findings are relevant for identifying types of landscapes where this conflict may arise and to better align respective policies.

Molecular evidence for three genetic species of Dipteryx in the Peruvian Amazon - Carmen Garcia-Davila; David Aldana Gomero; Jean-François Renno; Rossana Diaz Soria; Gabriel Hidalgo Pizango; Gerardo Flores Llampazo; Diana Castro-Ruiz; Eduardo Mejia de Loayza; Carlos Angulo Chavez; Malte Mader; Niklas Tysklind; Kathelyn Paredes-Villanueva; et al. (Genetica, 2020)

Will the emblematic southern conifer Araucaria angustifolia survive to climate change in Brazil? - Monik Begname Castro; Ana Carolina Maioli Campos Barbosa; Patrícia Vieira Pompeu; Pedro V. Eisenlohr; Gabriel de Assis Pereira; Deborah Mattos Guimarães Apgaua; João Carlos Pires-Oliveira; João Paulo Rodrigues Alves Delfino Barbosa; Marco Aurélio Leite Fontes; Rubens Manoel dos Santos; David Yue Phin Tng (Biodiversity and Conservation, 2020)

Mutational landscape and intra-host diversity of human papillomavirus type 16 long control region and E6 variants in cervical samples - Noé Escobar-Escamilla; Blanca Estela González-Martínez; Adnan Araiza-Rodríguez; David Esaú Fragoso-Fonseca; Abraham Pedroza-Torres; Magaly Guadalupe Landa-Flores; Fabiola Garcés-Ayala; Edgar Mendieta-Condado; José Alberto Díaz-Quiñonez; Graciela Castro-Escarpulli; José Ernesto Ramírez-González (Archives of Virology, 2019)

Climate change impact on a wine‐producing region using a dynamical downscaling approach: Climate parameters, bioclimatic indices and extreme indices - Daniel Blanco‐Ward; Alexandra Monteiro; Myriam Lopes; Carlos Borrego; Carlos Silveira; Carolina Viceto; Alfredo Rocha; António Ribeiro; João Andrade; Manuel Feliciano; João Castro; David Barreales; et al. (International Journal of Climatology, 2019)
Climate change is of major relevance to wine production as most of the wine‐growing regions of the world are located within relatively narrow latitudinal bands with average growing‐season temperatures (GSTs) limited to 13–21°C. This study focuses on the incidence of climate variables and indices that are relevant both for climate change assessment and for grape production, with emphasis on grapevine bioclimatic indices and extreme events (e.g., cold waves, storms, heatwaves). Dynamical downscaling of European Reanalysis‐Interim and Max Planck Institute Earth System low‐resolution global simulations forced with a Representative Concentration Pathway 8.5 (RCP8.5) greenhouse gas emission scenario was performed with the Weather Research and Forecast (WRF) model to a regional scale including the Douro Valley of Portugal for recent‐past (1986–2005) and future periods (2046–2065, 2081–2100). The number, duration and intensity of events were superimposed over critical phenological phases estimated by using a specific local grapevine varietal phenological model in order to assess their positive or negative implications for wine production in the region. An assessment of the relevance of climate parameters and indices and their progression in recent‐past and future climate scenarios with regard to the potential impact on wine production was performed. Results indicate a positive relation between higher growing‐season heat accumulations and greater vintage yields. A moderate incidence of very hot days (daily maximum temperature above 35°C) and drought from pre‐ véraison phenological conditions have a positive association with vintage ratings. However, the mid‐ and long‐term WRF‐MPI RCP8.5 future climate scenarios reveal shifts to warmer and drier conditions, with the mean GST not remaining within range for quality wine production in the long‐term future climate scenario. These results indicate potential impacts that suggest a range of strategies to maintain wine production and quality in the region.

First Record of Exotic Fish Canthidermis maculata (Bloch, 1786) (Pisces: Balistidae) in the Canary Islands (Central-East Atlantic) - Airam Guerra Marrero; David Jiménez Alvarado; José Juan Castro Hernández (Thalassas: An International Journal of Marine Sciences, 2019)

Prebiotic effect of Ulva rigida meal on the intestinal integrity and serum cholesterol and triglyceride content in broilers - Betsabé Cañedo-Castro; Alejandra Piñón-Gimate; Silvia Carrillo; David Ramos; Margarita Casas-Valdez (Journal of Applied Phycology, 2019)

Drought decreases incorporation of recent plant photosynthate into soil food webs regardless of their trophic complexity - Mathilde Chomel; Jocelyn M. Lavallee; Nil Alvarez‐Segura; Francisco de Castro; Jennifer M. Rhymes; Tancredi Caruso; Franciska T. de Vries; Elizabeth M. Baggs; Mark C. Emmerson; Richard D. Bardgett; David Johnson (Global Change Biology, 2019)
Theory suggests that more complex food webs promote stability and can buffer the effects of perturbations, such as drought, on soil organisms and ecosystem functions. Here, we tested experimentally how soil food web trophic complexity modulates the response to drought of soil functions related to carbon cycling and the capture and transfer below‐ground of recent photosynthate by plants. We constructed experimental systems comprising soil communities with one, two or three trophic levels (microorganisms, detritivores and predators) and subjected them to drought. We investigated how food web trophic complexity in interaction with drought influenced litter decomposition, soil CO 2 efflux, mycorrhizal colonization, fungal production, microbial communities and soil fauna biomass. Plants were pulse‐labelled after the drought with 13 C‐CO 2 to quantify the capture of recent photosynthate and its transfer below‐ground. Overall, our results show that drought and soil food web trophic complexity do not interact to affect soil functions and microbial community composition, but act independently, with an overall stronger effect of drought. After drought, the net uptake of 13 C by plants was reduced and its retention in plant biomass was greater, leading to a strong decrease in carbon transfer below‐ground. Although food web trophic complexity influenced the biomass of Collembola and fungal hyphal length, 13 C enrichment and the net transfer of carbon from plant shoots to microbes and soil CO 2 efflux were not affected significantly by varying the number of trophic groups. Our results indicate that drought has a strong effect on above‐ground–below‐ground linkages by reducing the flow of recent photosynthate. Our results emphasize the sensitivity of the critical pathway of recent photosynthate transfer from plants to soil organisms to a drought perturbation, and show that these effects may not be mitigated by the trophic complexity of soil communities, at least at the level manipulated in this experiment.

Current and Future Variations of the Monsoons of the Americas in a Warming Climate - Salvatore Pascale; Leila M. V. Carvalho; David K. Adams; Christopher L. Castro; Iracema F. A. Cavalcanti (Current Climate Change Reports, 2019)

Reproduction of the anthozoan Anemonia sulcata (Pennant, 1777) in southern Spain: from asexual reproduction to putative maternal care - Olga Utrilla; Juan Diego Castro-Claros; Javier Urra; Francisco David Navas; Carmen Salas (Marine Biology, 2019)

The acute phase response elicited by a viral-like molecular pattern increases energy expenditure in Artibeus lituratus - Camila Triana-Llanos; Adriana L. Guerrero-Chacón; David Rivera-Ruíz; Vladimir Rojas-Díaz; Andrea Niño-Castro (Biologia, 2019)

Echeveria sonianevadensis (Crassulaceae), una nueva especie del Volcán Nevado de Colima del occidente de México y una clave para la serie Gibbiflorae - H. David Jimeno-Sevilla; J. Antonio Vázquez-García; Miguel Ángel Muñiz-Castro; Ignacio García-Ruiz; Gerardo Hernández-Vera; y José Villa Castillo (Brittonia, 2019)

Historical photographs of captures of recreational fishers indicate overexploitation of nearshore resources at an oceanic island - David Jiménez‐Alvarado; Airam Sarmiento‐Lezcano; Airam Guerra‐Marrero; Fernando Tuya; Ángelo Santana Del Pino; Michael J. Sealey; José J. Castro (Journal of Fish Biology, 2019)
In this study, we used a historical collection of photographs taken by recreational fishers from 1940 to 2014, at the island of Gran Canaria, to show both a significant decrease in the mean total length of Epinephelus marginatus and a concurrent change in the composition of captures. Before 1980, the mean total length of fish caught and photographed was c . 100 cm, while after 2009 this was typically E. marginatus (an apex predator), but currently the majority of catches are of omnivorous species, in particular the parrotfish, Sparisoma cretense and seabreams Diplodus spp. Overall, integration of these results indicates a qualitative and quantitative variation in captures of recreational fishers, probably as a sign of change in ecological balances and the overfished status of many target species.

Temporal and spatial predictions of effect of alternative fishing policies for the Gran Canaria marine ecosystem - Lorena Couce Montero; Villy Christensen; Alberto Bilbao Sieyro; Yeray Pérez González; David Jiménez‐Alvarado; José J. Castro (Journal of Fish Biology, 2019)
In this paper we consider what may happen to the marine ecosystem of Gran Canaria Island within the 2030 horizon, if fishing strategies different from those currently in place were implemented and we evaluate the effect of, for example, reduction of recreational–artisanal fishing, limitation of catches ( e.g . total allowable catches, TAC), or spatial distribution of fishing sectors. From all scenarios tested, only those that significantly reduce the high effort of the recreational fishing would allow the recovery of the most exploited stocks in the marine ecosystem in the short and medium‐term. Moreover, the best management strategy, in contribution to abundance, was obtained with a scenario that has a spatial partition of exploitation rights between artisanal and recreational fishermen and includes no‐fishing zones (NTZ). This work is a first attempt to use spatial and temporal models to assess the effectiveness of alternative fishery policies in the Canary Islands.

Topical anti-inflammatory activity in TPA-induced mouse ear edema model and in vitro antibacterial properties of Cordia alba flowers - Jenny Castro; David Rivera; Luis A. Franco (Journal of Pharmaceutical Investigation, 2019)

Upstream refugia and dispersal ability may override benthic-community responses to high-Andean streams deforestation - Juan David González-Trujillo; Danielle K. Petsch; Gabriela Córdoba-Ariza; Katterine Rincón-Palau; Jhon Ch. Donato-Rondon; Maria I. Castro-Rebolledo; Sergi Sabater (Biodiversity and Conservation, 2019)

Porosity Estimation and Geometric Characterization of Fractured and Karstified Carbonate Rocks Using GPR Data in the Salitre Formation, Brazil - Iurianne M. M. Conti; David L. de Castro; Francisco H. R. Bezerra; Caroline L. Cazarin (Pure and Applied Geophysics, 2019)

Draft genome sequence of Lactobacillus plantarum C4 (CECT 9567), a potential probiotic strain isolated from kefir - Soumi De Montijo-Prieto; David J. Castro; Jose C. Reina; Maria Jimenez-Valera; Alfonso Ruiz-Bravo (Archives of Microbiology, 2019)

Cryopreserved potato shoot tips showed genotype-specific response to sucrose concentration in rewarming solution (RS) - Rainer Vollmer; Rosalva Villagaray; Mario Castro; Noelle L. Anglin; David Ellis (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Drought in Southern California coastal sage scrub reduces herbaceous biomass of exotic species more than native species, but exotic growth recovers quickly when drought ends - Chandler E. Puritty; Ellen H. Esch; Sherlynette Pérez Castro; Elizabeth M. Ryan; David A. Lipson; Elsa E. Cleland (Plant Ecology, 2019)

CHEMICAL CHARACTERIZATION OF A NEW ACIDIFIED REGION TO STUDY OCEAN ACIDIFICATION IN SUBTROPICAL ECOSYSTEMS - Sara González-Delgado; J. Magdalena Casiano; MELCHOR GONZALEZ-DAVILA; David González-Santana; Celso Hernández; Enrique Lozano-Bilbao; Adrian Castro; Carlos Sangil; José Carlos Hernández (Frontiers in Marine Science, 2019)

Meristic differences between juveniles of two tuna species from the Western Mediterranean Sea. - Jairo Castro-Gutiérrez; Samar Saber; Josetxu Ortiz De Urbina; María Gómez-Vives; Salvador García-Barcelona; David Macías (Frontiers in Marine Science, 2019)

The PERCEBES project: science for the spatial management of the stalked barnacle fishery in the Atlantic Arc - Katja Geiger; José Luis Acuña; Alba Aguión; Arrontes Julio; Marion Ballenghiem; Yaisel J. Borrell; Caroline Broudin; João Castro; Juliette Chiss; Teresa Cruz; Dominique Davoult; Jesus Dubert; et al. (Frontiers in Marine Science, 2019)

Morphological and quality variation of the stalked barnacle Pollicipes pollicipes (Gmelin, 1970) - Alina Sousa; David Jacinto; Nélia Penteado; Diana Pereira; Teresa Silva; João Castro; Teresa Cruz (Frontiers in Marine Science, 2019)

The stalked barnacle Pollicipes pollicipes fishery at Reserva Natural das Berlengas (Portugal): temporal variation of the harvesters perspective - Alina Sousa; David Jacinto; Nélia Penteado; Diana Pereira; Teresa Silva; João Castro; Sergio Leandro; Teresa Cruz (Frontiers in Marine Science, 2019)

ACUSQUAT Project: Acoustic behavioural monitoring of the Angelshark (Squatina squatina) in critical conservation areas - Diego Campos; David Jiménez-Alvarado; José Juan Castro-Hernández; Airam Guerra-Marrero; Jorge Cabrera-Gámez; Antonio Domínguez-Brito (Frontiers in Marine Science, 2019)

Effects of hydrodynamic conditions and feeding period on size, growth and cirral behavior of the stalked-barnacle Pollicipes pollicipes - Maria Inês Seabra; Maria Santos; David Jacinto; David Mateus; Joana Fernandes; Ana Pombo; Teresa Silva; João Castro; Teresa Cruz (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

HERC1 Ubiquitin Ligase Is Required for Normal Axonal Myelination in the Peripheral Nervous System - Sara Bachiller; María Angustias Roca-Ceballos; Irene García-Domínguez; Eva María Pérez-Villegas; David Martos-Carmona; Miguel Ángel Pérez-Castro; Luis Miguel Real; José Luis Rosa; Lucía Tabares; José Luis Venero; José Ángel Armengol; Ángel Manuel Carrión; et al. (Molecular Neurobiology, 2018)

Metabolic cost of acute phase response in the frugivorous bat, Artibeus lituratus - Adriana L. Guerrero-Chacón; David Rivera-Ruíz; Vladimir Rojas-Díaz; Camila Triana-Llanos; Andrea Niño-Castro (Mammal Research, 2018)

Exploring drivers of litter decomposition in a greening Arctic: results from a transplant experiment across a treeline - Thomas C. Parker; Jonathan Sanderman; Robert D. Holden; Gesche Blume‐Werry; Sofie Sjögersten; David Large; Miguel Castro‐Díaz; Lorna E. Street; Jens‐Arne Subke; Philip A. Wookey (Ecology, 2018)
Decomposition of plant litter is a key control over carbon (C) storage in the soil. The biochemistry of the litter being produced, the environment in which the decomposition is taking place, and the community composition and metabolism of the decomposer organisms exert a combined influence over decomposition rates. As deciduous shrubs and trees are expanding into tundra ecosystems as a result of regional climate warming, this change in vegetation represents a change in litter input to tundra soils and a change in the environment in which litter decomposes. To test the importance of litter biochemistry and environment in determining litter mass loss, we reciprocally transplanted litter between heath ( Empetrum nigrum ), shrub ( Betula nana ), and forest ( Betula pubescens ) at a sub‐Arctic treeline in Sweden. As expansion of shrubs and trees promotes deeper snow, we also used a snow fence experiment in a tundra heath environment to understand the importance of snow depth, relative to other factors, in the decomposition of litter. Our results show that B. pubescens and B. nana leaf litter decomposed at faster rates than E. nigrum litter across all environments, while all litter species decomposed at faster rates in the forest and shrub environments than in the tundra heath. The effect of increased snow on decomposition was minimal, leading us to conclude that microbial activity over summer in the productive forest and shrub vegetation is driving increased mass loss compared to the heath. Using B. pubescens and E. nigrum litter, we demonstrate that degradation of carbohydrate‐C is a significant driver of mass loss in the forest. This pathway was less prominent in the heath, which is consistent with observations that tundra soils typically have high concentrations of “labile” C. This experiment suggests that further expansion of shrubs and trees may stimulate the loss of undecomposed carbohydrate C in the tundra.

Characterization of esterase activity from an Acetomicrobium hydrogeniformans enzyme with high structural stability in extreme conditions - Patricia S. Kumagai; Raissa F. Gutierrez; Jose L. S. Lopes; Julia M. Martins; David M. Jameson; Aline M. Castro; Luiz F. Martins; Ricardo DeMarco; Nelma R. S. Bossolan; B. A. Wallace; Ana P. U. Araujo (Extremophiles, 2018)

Quantitative trait loci associated with trichomes in the Solanum galapagense accession LA1401 - Marcela Carvalho Andrade; Alex Antônio da Silva; Regis de Castro Carvalho; Juliana de Andrade Santiago; Alisson Marcel Souza de Oliveira; David Merrill Francis; Wilson Roberto Maluf (Genetic Resources and Crop Evolution, 2018)

Geostatistical Interplay Between Geophysical and Geochemical Data: Mapping Litho-Structural Assemblages of Mesozoic Igneous Activities in the Parnaíba Basin (NE Brazil) - David L. de Castro; Diógenes C. Oliveira; Maria Helena B. M. Hollanda (Surveys in Geophysics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Behavior of Micropollutants in Polishing Units that Combine Sorption and Biodegradation Mechanisms to Improve the Quality of Activated Sludge Effluent - Lucas Vassalle de Castro; Emanuel Manfred Freire Brandt; Alexandre Cristiano Vicente Campos; Sérgio Francisco de Aquino; David Werner; Robson José de Cassia Franco Afonso; Cesar Rossas Mota Filho (Water, Air, & Soil Pollution, 2018)

Comparison of four modeling tools for the prediction of potential distribution for non-indigenous weeds in the United States - Roger Magarey; Leslie Newton; Seung Cheon Hong; Yu Takeuchi; David Christie; Catherine S. Jarnevich; Lisa Kohl; Martin Damus; Steven I. Higgins; Leah Millar; Karen Castro; Amanda West; et al. (Biological Invasions, 2018)

The future of fish passage science, engineering, and practice - Ana T. Silva; Martyn C. Lucas; Theodore Castro‐Santos; Christos Katopodis; Lee J. Baumgartner; Jason D. Thiem; Kim Aarestrup; Paulo S. Pompeu; Gordon C. O'Brien; Douglas C. Braun; Nicholas J. Burnett; David Z. Zhu; et al. (Fish and Fisheries, 2018)
Much effort has been devoted to developing, constructing and refining fish passage facilities to enable target species to pass barriers on fluvial systems, and yet, fishway science, engineering and practice remain imperfect. In this review, 17 experts from different fish passage research fields (i.e., biology, ecology, physiology, ecohydraulics, engineering) and from different continents (i.e., North and South America, Europe, Africa, Australia) identified knowledge gaps and provided a roadmap for research priorities and technical developments. Once dominated by an engineering‐focused approach, fishway science today involves a wide range of disciplines from fish behaviour to socioeconomics to complex modelling of passage prioritization options in river networks. River barrier impacts on fish migration and dispersal are currently better understood than historically, but basic ecological knowledge underpinning the need for effective fish passage in many regions of the world, including in biodiversity hotspots (e.g., equatorial Africa, South‐East Asia), remains largely unknown. Designing efficient fishways, with minimal passage delay and post‐passage impacts, requires adaptive management and continued innovation. While the use of fishways in river restoration demands a transition towards fish passage at the community scale, advances in selective fishways are also needed to manage invasive fish colonization. Because of the erroneous view in some literature and communities of practice that fish passage is largely a proven technology, improved international collaboration, information sharing, method standardization and multidisciplinary training are needed. Further development of regional expertise is needed in South America, Asia and Africa where hydropower dams are currently being planned and constructed.

Effect of food density and hydrodynamic conditions on the survival and growth of the stalked barnacle Pollicipes pollicipes - Ana Torres; Ana Pombo; Joana Fernandes; Daniela Nobre; Maria Seabra; Teresa Silva; João Castro; Sofia Franco; Anthony Clare; David Jacinto; Teresa Cruz (Frontiers in Marine Science, 2018)

A large-scale viability assessment of the potato cryobank at the International Potato Center (CIP) - Rainer Vollmer; Rosalva Villagaray; José Cárdenas; Mario Castro; Oswaldo Chávez; Noelle L. Anglin; David Ellis (In Vitro Cellular & Developmental Biology - Plant, 2017)

Assessment of azole fungicides as a tool to control growth of Aspergillus flavus and aflatoxin B 1 and B 2 production in maize - Eva M. Mateo; José Vicente Gómez; José Vicente Gimeno-Adelantado; David Romera; Rufino Mateo-Castro; Misericordia Jiménez (Food Additives & Contaminants: Part A, 2017)

Streptomyces aridus sp. nov., isolated from a high altitude Atacama Desert soil and emended description of Streptomyces noboritoensis Isono et al. 1957 - Hamidah Idris; David P. Labeda; Imen Nouioui; Jean Franco Castro; Maria del Carmen Montero-Calasanz; Alan T. Bull; Juan A. Asenjo; Michael Goodfellow (Antonie van Leeuwenhoek, 2017)

Inheritance of type IV glandular trichome density and its association with whitefly resistance from Solanum galapagense accession LA1401 - Marcela Carvalho Andrade; Alex Antônio da Silva; Irã Pinheiro Neiva; Izabela Regina C. Oliveira; Evaristo Mauro De Castro; David Merrill Francis; Wilson Roberto Maluf (Euphytica, 2017)

Erratum to: Anosmin-1 over-expression increases adult neurogenesis in the subventricular zone and neuroblast migration to the olfactory bulb - Diego García-González; Verónica Murcia-Belmonte; Pedro F. Esteban; Felipe Ortega; David Díaz; Irene Sánchez-Vera; Rafael Lebrón-Galán; Laura Escobar-Castañondo; Luis Martínez-Millán; Eduardo Weruaga; José Manuel García-Verdugo; Benedikt Berninger; et al. (Brain Structure and Function, 2016)

Assessing the extent and nature of wildlife trade on the dark web - Joseph R. Harrison; David L. Roberts; Julio Hernandez‐Castro (Conservation Biology, 2016)
Use of the internet as a trade platform has resulted in a shift in the illegal wildlife trade. Increased scrutiny of illegal wildlife trade has led to concerns that online trade of wildlife will move onto the dark web. To provide a baseline of illegal wildlife trade on the dark web, we downloaded and archived 9852 items (individual posts) from the dark web, then searched these based on a list of 121 keywords associated with illegal online wildlife trade, including 30 keywords associated with illegally traded elephant ivory on the surface web. Results were compared with items known to be illegally traded on the dark web, specifically cannabis, cocaine, and heroin, to compare the extent of the trade. Of these 121 keywords, 4 resulted in hits, of which only one was potentially linked to illegal wildlife trade. This sole case was the sale and discussion of Echinopsis pachanoi (San Pedro cactus), which has hallucinogenic properties. This negligible level of activity related to the illegal trade of wildlife on the dark web relative to the open and increasing trade on the surface web may indicate a lack of successful enforcement against illegal wildlife trade on the surface web.

Stream noise, habitat filtering, and the phenotypic and phylogenetic structure of Neotropical anuran assemblages - Juan David Carvajal-Castro; Fernando Vargas-Salinas (Evolutionary Ecology, 2016)

Environmental flow in the River Ondas basin in Bahia, Brazilian Cerrado - Elis Regina Rodrigues de Souza Castro; Michel Castro Moreira; Demetrius David da Silva (Environmental Monitoring and Assessment, 2016)

Anosmin-1 over-expression increases adult neurogenesis in the subventricular zone and neuroblast migration to the olfactory bulb - Diego García-González; Verónica Murcia-Belmonte; Pedro F. Esteban; Felipe Ortega; David Díaz; Irene Sánchez-Vera; Rafael Lebrón-Galán; Laura Escobar-Castañondo; Luis Martínez-Millán; Eduardo Weruaga; José Manuel García-Verdugo; Benedikt Berninger; et al. (Brain Structure and Function, 2016)

The stalked barnacle (Pollicipes pollicipes) fishery, management, conservation and aquaculture in Portugal: problems and challenges - Cruz Teresa; Jacinto David; Fernandes Joana; Seabra Maria; Silva Teresa; Franco Sofia; Castro João (Frontiers in Marine Science, 2016)

Polychaete annelids as live bait in Portugal: harvesting activity in estuarine systems - Cabral Sara; Alves Ana; Castro Nuno; Fidalgo E Costa Pedro; Sá Erica; Castro João; Cancela Da Fonseca Luís; Chainho Paula; Canning-Clode João; Picard David; Pombo Ana; Costa José Lino (Frontiers in Marine Science, 2016)

Ovarian activity and estrus behavior in early postpartum cows grazing Leucaena leucocephala in the tropics - Maria Bottini-Luzardo; Carlos Aguilar-Perez; Fernando Centurion-Castro; Francisco Solorio-Sanchez; Armin Ayala-Burgos; Ruben Montes-Perez; David Muñoz-Rodriguez; Juan Ku-Vera (Tropical Animal Health and Production, 2015)

Use of an abandoned gravel-pit in inland Spain as a stopover site for the Aquatic Warbler Acrocephalus paludicola - David Miguélez; Javier García; Víctor Castro; Benito Fuertes; Carlos Zumalacárregui; Rubén González-Jáñez (Wetlands Ecology and Management, 2015)

Trophoblast expression dynamics of the tumor suppressor gene gastrokine 2 - Fabian B. Fahlbusch; Matthias Ruebner; Hanna Huebner; Gudrun Volkert; Hannah Bartunik; Ilona Winterfeld; Andrea Hartner; Carlos Menendez-Castro; Stephanie C. Noegel; Ines Marek; David Wachter; Regine Schneider-Stock; et al. (Histochemistry and Cell Biology, 2015)

Report of outbreaks of classical scrapie in Dorper sheep and associated prion protein gene polymorphisms in affected flocks - Caroline Pinto de Andrade; Eduardo Conceição de Oliveira; Juliano Souza Leal; Laura Lopes de Almeida; Luiza Amaral de Castro; Sergio Ceroni da Silva; David Driemeier (Tropical Animal Health and Production, 2015)

Footprints in the sand: a persistent spatial impression of fishing in a mobile groundfish assemblage - Francisco de Castro; Samuel Shephard; Sarah B. M. Kraak; David G. Reid; Keith D. Farnsworth (Marine Biology, 2015)

Genetic mapping of QTL for maize weevil resistance in a RIL population of tropical maize - Fernando F. Castro-Álvarez; Manilal William; David J. Bergvinson; Silverio García-Lara (Theoretical and Applied Genetics, 2015)

Characterization of ANKRD11 mutations in humans and mice related to KBG syndrome - Katherina Walz; Devon Cohen; Paul M. Neilsen; Joseph Foster; Francesco Brancati; Korcan Demir; Richard Fisher; Michelle Moffat; Nienke E. Verbeek; Kathrine Bjørgo; Adriana Lo Castro; Paolo Curatolo; et al. (Human Genetics, 2015)

Portable chlorophyll meter (PCM-502) values are related to total chlorophyll concentration and photosynthetic capacity in papaya (Carica papaya L.) - Fernanda Assumpção De Castro; Eliemar Campostrini; Alena Torres Netto; Mara De Menezes De Assis Gomes; Tiago Massi Ferraz; David Michael Glenn (Theoretical and Experimental Plant Physiology, 2014)

Biogeography and conservation of aquatic fauna in spring-fed tropical canyons of the southern Sonoran Desert, Mexico - Michael T. Bogan; Nohemí Noriega-Felix; Sylvette Leonor Vidal-Aguilar; Lloyd T. Findley; David A. Lytle; Oscar G. Gutiérrez-Ruacho; J. Andrés Alvarado-Castro; Alejandro Varela-Romero (Biodiversity and Conservation, 2014)

Applying Water Vulnerability Indexes for River Segments - Weriskiney Araújo Almeida; Michel Castro Moreira; Demetrius David da Silva (Water Resources Management, 2014)

Witnessing North Atlantic westerlies variability from ships’ logbooks (1685–2008) - David Barriopedro; David Gallego; M. Carmen Alvarez-Castro; Ricardo García-Herrera; Dennis Wheeler; Cristina Peña-Ortiz; Susana M. Barbosa (Climate Dynamics, 2014)

Sea urchins, their predators and prey in SW Portugal - Mamede Nuno; Jacinto David; Cruz Teresa; Castro João (Frontiers in Marine Science, 2014)

Echeveria yalmanantlanensis (Crassulaceae): A new species from Cerro Grande, Sierra de Manantlán, western Mexico - J. Antonio Vázquez-García; David Jimeno-S.; Ramón Cuevas-G.; Miguel Cházaro-B.; Miguel A. Muñiz-Castro (Brittonia, 2013)

E. coli outbreak in a neonate intensive care unit in a general hospital in Mexico City - Erika Margarita Carrillo-Casas; Zaydy Suástegui-Urquijo; Sara Arroyo-Escalante; Rosario Morales-Espinosa; David Moncada-Barrón; Lorena Hernández-Delgado; José Luis Méndez-Sánchez; Gabriela Delgado-Sapién; Armando Navarro-Ocaña; Ángel Manjarrez-Hernández; Juan Xicohtencatl-Cortes; Rigoberto Hernández-Castro (Folia Microbiologica, 2013)

Influence of fine woody debris on spider diversity and community structure in forest leaf litter - Alberto Castro; David H. Wise (Biodiversity and Conservation, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Marine extinctions revisited - Pablo del Monte‐Luna; Daniel Lluch‐Belda; Elisa Serviere‐Zaragoza; Roberto Carmona; Héctor Reyes‐Bonilla; David Aurioles‐Gamboa; José Luis Castro‐Aguirre; Sergio A. Guzmán del Próo; Oscar Trujillo‐Millán; Barry W. Brook (Fish and Fisheries, 2007)
In recent years, more than 130 extinctions have been estimated to have occurred in the marine realm. Here we review this body of evidence and show that this figure may actually be overestimated by as much as 50%. We argue that previous estimates have not fully taken into account critical uncertainties such as naturally variable geographical distributions, and have misinterpreted documentary evidence. However, current evidence indicates that some sharks, rays and reef‐associated species, although not necessarily geographically restricted, are particularly vulnerable to anthropogenic impacts and now occur in very low numbers. Overestimating extinctions is of concern because it could reduce confidence in the credibility of the ‘extinct’ category in threatened species lists and, ultimately, be used to question the integrity of conservation and management policies. We suggest that when integrating future checklists of marine extinct species, there needs to be a more rigorous use of the terminology of extinction, and participation by specialists in each of the particular taxonomic groups involved.

Mercury Resistance in Bacterial Strains Isolated from Tailing Ponds in a Gold Mining Area Near El Callao (Bolívar State, Venezuela) - María Mercedes Ball; Pablo Carrero; David Castro; Luis Andrés Yarzábal (Current Microbiology, 2007)

Relation of dental wear to the concentrations of essential minerals in teeth of the California sea lion Zalophus Californianus Californianus - Vanessa Labrada-Martagón; David Aurioles-Gamboa; Ma. Isabel Castro-González (Biological Trace Element Research, 2007)

Relation of dental wear to the concentrations of essential minerals in teeth of the California sea lion Zalophus Californianus Californianus - Vanessa Labrada-Martagón; David Aurioles-Gamboa; Ma. Isabel Castro-González (Biological Trace Element Research, 2007)

Fate of carbon in upland grassland subjected to liming using in situ 13CO2 pulse-labelling - Bente Foereid; Lorna A. Dawson; David Johnson; J. Ignacio Rangel-Castro (Plant and Soil, 2006)

North Atlantic oscillation influence on precipitation, river flow and water resources in the Iberian Peninsula - Ricardo M. Trigo; David Pozo‐Vázquez; Timothy J. Osborn; Yolanda Castro‐Díez; Sonia Gámiz‐Fortis; María Jesus Esteban‐Parra (International Journal of Climatology, 2004)
The Iberian Peninsula precipitation and river flow regimes are characterized by large values of inter‐annual variability, with large disparities between wet and dry years, especially in southern Iberia. This situation is a major problem for water resources management in general, and for the production of hydroelectricity in particular. Hydroelectric production represents, in an average year of precipitation, 20% of the total Spanish electricity production (and 35% for Portuguese production). Its absolute value, however, can vary by a factor of three between wet and dry years. We have assessed the impact of the North Atlantic oscillation (NAO) on winter precipitation and river flow regimes for the three main international Iberian river basins, namely the Douro (north), the Tejo (centre) and the Guadiana (south). Results show that the large inter‐annual variability in the flows of these three rivers is largely modulated by the NAO phenomenon. Throughout most of the 20th century, the January‐to‐March river flow is better correlated with the December to February (DJF) NAO index than is the simultaneous (DJF) river flow. Correlation values for the period 1973–98 are highly significant (−0.76 for Douro, −0.77 for Tejo and −0.79 for Guadiana), being consistently of higher magnitude than those obtained over previous decades. This impact of the NAO on winter river flow was quantified in terms of total Spanish potential hydroelectricity production. The important control exerted by the NAO and the recent positive trend in the NAO index contribute to a significant decrease in the available flow. This reduction represents an important hazard for the two Iberian economies because of its negative impact on water‐dependent resources, such as intensive agriculture and hydroelectric power production. Copyright © 2004 Royal Meteorological Society

Effect of Extra-Pair Paternity on Effective Population Size in a Reintroduced Population of the Endangered Hihi, and Potential for Behavioural Management - Isabel Castro; Karen M. Mason; Doug P. Armstrong; David M. Lambert (Conservation Genetics, 2004)

Quantifying mortality of tropical rain forest trees using high‐spatial‐resolution satellite data - David B. Clark; Carlomagno Soto Castro; Luis Diego Alfaro Alvarado; Jane M. Read (Ecology Letters, 2004)
Assessment of forest responses to climate change is severely hampered by the limited information on tree death on short temporal and broad spatial scales, particularly in tropical forests. We used 1‐m resolution panchromatic IKONOS and 0.7‐m resolution QuickBird satellite data, acquired in 2000 and 2002, respectively, to evaluate tree death rates at the La Selva Biological Station in old‐growth Tropical Wet Forest in Costa Rica, Central America. Using a calibration factor derived from ground inspection of tree deaths predicted from the images, we calculated a landscape‐scale annual exponential death rate of 2.8%. This corresponds closely to data for all canopy‐level trees in 18 forest inventory plots, each of 0.5 ha, for a mostly‐overlapping 2‐year period (2.8% per year). This study shows that high‐spatial‐resolution satellite data can now be used to measure old‐growth tropical rain forest tree death rates, suggesting many new avenues for tropical forest ecology and global change research.

Luis A. Carneiro - Rui Oliveira; David Gonçalves; Joana Jordão; Albert Ros; Katharina Hirschenhauser; Teresa Fagundes; Tânia Oliveira; Rui Andrade; João Saraiva; Ana Silva; Nídia Castro; Lúcia Costa (acta ethologica, 2003)

A LIMITED-LENGTH-SCALE k-ε MODEL FOR THE NEUTRAL AND STABLY-STRATIFIED ATMOSPHERIC BOUNDARY LAYER - DAVID D. APSLEY; IAN P. CASTRO (Boundary-Layer Meteorology, 1997)